Method for producing a protected negative electrode and the resulting negative electrode

By preparing a lithium affinity organometallic coating on the surface of the negative electrode material of the lithium-ion battery, the problems of insufficient safety of liquid electrolytes and the reactivity of solid electrolytes are solved, and the stability and energy density of the battery are improved.

JP2025504492APending Publication Date: 2025-02-12HYDRO QUEBEC CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024543336
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-28
Filing Date
2023-01-27
Publication Date
2025-02-12

AI Technical Summary

Technical Problem

The liquid electrolyte in the existing lithium-ion battery is flammable and the formation of the SEI layer consumes lithium ions, reducing battery efficiency. The metal negative electrode deforms during the cycle to form lithium dendrites, resulting in a short circuit, and the solid electrolyte has problems such as insufficient reactivity and ionic conductivity.

Method used

A coating containing a lithium affinity organometallic structure is prepared on the surface of the negative electrode material. The coating material is formed by contacting the organic ligand with the lithium ion metal precursor and calcining it and depositing it on the surface of the active material, and a protective layer is formed by printing or spraying.

Benefits of technology

It improves the stability of the negative electrode material, reduces the growth of lithium dendrites, enhances the safety and energy density of the battery, and improves the reactivity and contactability of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504492000001_ABST
    Figure 2025504492000001_ABST
Patent Text Reader

Abstract

A negative electrode material is described that includes an electrochemically active material and a coating layer on the surface thereof. The coating layer includes a coating material based on a calcined lithiophilic organometallic structure that includes at least one lithiophilic metal and at least one at least partially calcined organic ligand. A method for producing the electrode material, an electrode including the material, and their use in electrochemical cells and batteries are also described. According to another aspect, the present technology relates to a negative electrode material that includes an electrochemically active material and a coating layer that includes a coating material based on a calcined lithiophilic organometallic structure that includes at least one lithiophilic metal and at least one at least partially calcined organic ligand, the coating layer being disposed on the surface of the electrochemically active material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Related Applications This application claims priority under applicable law to Canadian Provisional Patent Application No. 3,147,039, filed January 28, 2022, the contents of which are incorporated herein by reference in their entirety for all purposes.

[0002] Technical Field The present technology relates to the field of negative electrode materials comprising a coating layer on one of their surfaces, electrodes comprising them, methods for preparing these materials, and their use in electrochemical cells. [Background technology]

[0003] background The liquid electrolytes used in lithium-ion batteries are flammable and slowly decompose to form a passivation layer on the surface of the lithium film, known as the solid electrolyte interface (SEI), which irreversibly consumes lithium and reduces the coulombic efficiency of the battery. Furthermore, the lithium anode undergoes significant morphological changes during battery cycling, leading to the formation of lithium dendrites. These typically migrate through the electrolyte and can eventually cause short circuits.

[0004] Safety concerns and the requirement for higher energy density have driven research into the development of all-solid-state rechargeable lithium batteries containing polymer or ceramic type electrolytes, both of which are more stable relative to lithium metal and reduce the growth of lithium dendrites. However, certain disadvantages arise from the use of such solid electrolytes, such as loss of reactivity or ionic conductivity, poor contact between solid interfaces, etc.

[0005] As a result, there is a need to develop new methods for protecting the surfaces of metal electrodes. Summary of the Invention [Means for solving the problem]

[0006] overview According to one aspect, the present technology provides a method for preparing a negative electrode material comprising an electrochemically active material and a coating layer comprising a calcined lithiophile organometallic structure-based coating material disposed on a surface of the electrochemically active material, the method comprising the steps of: (i) contacting at least one organic ligand with at least one lithiophilic metal precursor to obtain a lithiophilic organometallic structure; (ii) calcining the lithiophilic organometallic structure obtained in (i) to obtain a calcined lithiophilic organometallic structure of the coating material; (iii) depositing a coating material on the surface of the electrochemically active material; The present invention relates to a method comprising the steps of:

[0007] In one embodiment, the lithiophilic metal is selected from Ag, Zn, Sn, Sb, Mg, Al, Ni, Cu, Co, and combinations of at least two thereof.

[0008] In another embodiment, the organic ligand is an organic ligand containing a nitrogen functionality, an organic ligand containing a carboxylate, or a mixed organic ligand containing a nitrogen functionality and / or a carboxylate. According to one example, the organic ligand is 1,2,4,5-benzenetetracarboxylic acid or 1H-benzimidazole-6-carboxylic acid.

[0009] In another embodiment, the lithiophilic organometallic structure obtained in (i) has the formula 1: [ka] It is of the following.

[0010] In another embodiment, the lithiophilic organometallic structure obtained in (i) is represented by formula 2: [ka] It is of the following.

[0011] In another embodiment, the lithiophilic organometallic structure obtained in (i) is represented by formula 3: [ka] It is of the following.

[0012] In another embodiment, the lithiophilic organometallic structure obtained in (i) is represented by formula 4: [ka] It is of the following.

[0013] In another embodiment, the lithiophilic organometallic structure obtained in (i) is represented by formula 5: [ka] It is of the following.

[0014] In another embodiment, the lithiophilic organometallic structure obtained in (i) is represented by formula 6: [ka] (In the formula, n1 and n2 indicate the ratio of each unit and are independently selected numbers ranging from 0.1 to 0.9. It is of the following.

[0015] In another embodiment, the lithiophilic organometallic structure obtained in (i) is represented by formula 7: [ka] (In the formula, n1 and n2 indicate the ratio of each unit and are independently selected numbers ranging from 0.1 to 0.9. It is of the following.

[0016] In another embodiment, the lithiophilic organometallic structure obtained in (i) is represented by formula 8: [ka] (In the formula, n1 and n2 indicate the ratio of each unit and are independently selected numbers ranging from 0.1 to 0.9. It is of the following.

[0017] In another embodiment, the lithiophilic organometallic structure obtained in (i) is represented by formula 9: [ka] It is of the following.

[0018] In another embodiment, the calcination step is carried out at a temperature between about 500° C. and about 1050° C. According to one example, the calcination step is carried out at a temperature between about 550° C. and about 1000° C.

[0019] In another embodiment, the calcination step is carried out under an inert atmosphere. According to one example, the inert atmosphere comprises a gas selected from argon, oxygen, nitrogen, helium, fluoride gas, and mixtures comprising at least two of them. According to one example of the object, the inert atmosphere comprises argon.

[0020] In another embodiment, the depositing step is performed by at least one of a printing method such as doctor blade coating, comma coating, reverse comma coating, gravure coating, slot die coating, or spray deposition. According to one example, the depositing step is performed by spray deposition.

[0021] In another embodiment, the method further comprises depositing a second coating layer.

[0022] According to one example, the step of depositing the second coating layer is performed by at least one of a printing method such as doctor blade coating, comma coating, reverse comma coating, gravure coating, a slot die coating, or a spray deposition method. According to one example of the object, the step of depositing the second coating layer is performed by a spray deposition method.

[0023] According to another aspect, the present technology relates to a negative electrode material obtained according to the method as defined herein.

[0024] According to another aspect, the present technology relates to a negative electrode material comprising an electrochemically active material and a coating layer comprising a coating material based on a calcined lithiophilic organometallic structure comprising at least one lithiophilic metal and at least one at least partially calcined organic ligand, wherein the coating layer is disposed on a surface of the electrochemically active material.

[0025] In one embodiment, the electrochemically active material includes an alkali metal, an alkaline earth metal, a non-alkali and non-alkaline earth metal, or an alloy including at least one of them. According to one example, the electrochemically active material includes an alkali metal, an alkaline earth metal, or an alloy including at least one alkali or alkaline earth metal. For example, the electrochemically active material includes metallic lithium, or an alloy including or based on metallic lithium. According to another example, the electrochemically active material includes nickel.

[0026] In another embodiment, the electrochemically active material is in the form of a film having a thickness ranging from about 5 μm to about 75 μm, or from about 15 μm to about 70 μm, or from about 25 μm to about 65 μm, or from about 30 μm to about 60 μm, or from about 45 μm to about 55 μm, including the upper and lower limits.

[0027] In another embodiment, the lithiophilic metal is selected from Ag, Zn, Sn, Sb, Mg, Al, Ni, Cu, Co, and combinations of at least two thereof.

[0028] In another embodiment, the organic ligand is a nitrogen-functional organic ligand, a carboxylate-functional organic ligand, or a mixed nitrogen-functional and / or carboxylate-functional organic ligand. According to one example, the organic ligand is 1,2,4,5-benzenetetracarboxylic acid or 1H-benzimidazole-6-carboxylic acid.

[0029] In another embodiment, the lithiophilic organometallic structure prior to calcination is represented by Formula 1: [ka] It is of the following.

[0030] In another embodiment, the lithiophilic organometallic structure prior to calcination is represented by Formula 2: [ka] It is of the following.

[0031] In another embodiment, the lithiophilic organometallic structure prior to calcination is represented by Formula 3: [ka] It is of the following.

[0032] In another embodiment, the lithiophilic organometallic structure prior to calcination is represented by Formula 4: [ka] It is of the following.

[0033] In another embodiment, the lithiophilic organometallic structure prior to calcination is represented by formula 5: [ka] It is of the following.

[0034] In another embodiment, the lithiophilic organometallic structure prior to calcination is represented by formula 6: [ka] (In the formula, n1 and n2 indicate the ratio of each unit and are independently selected numbers ranging from 0.1 to 0.9. It is of the following.

[0035] In another embodiment, the lithiophilic organometallic structure prior to calcination is represented by formula 7: [ka] (In the formula, n1 and n2 indicate the ratio of each unit and are independently selected numbers ranging from 0.1 to 0.9. It is of the following.

[0036] In another embodiment, the lithiophilic organometallic structure prior to calcination is represented by formula 8: [ka] (In the formula, n1 and n2 indicate the ratio of each unit and are independently selected numbers ranging from 0.1 to 0.9. It is of the following.

[0037] In another embodiment, the lithiophilic organometallic structure prior to calcination is represented by formula 9: [ka] It is of the following.

[0038] In another embodiment, the calcined lithiophilic organometallic structure further comprises a silver source. According to a variation of interest, the silver source is a silver salt. According to one example, the silver salt is AgCl or AgNO3. According to another example, the salt is present in a lithiophilic metal:silver ratio ranging from about 4:3 to about 4:1, including upper and lower limits.

[0039] In another embodiment, the coating material further comprises a solid polymer electrolyte comprising a salt in a solvated polymer.

[0040] According to one example, the solid polymer electrolyte is a copolymer of ethylene oxide and at least one substituted oxirane containing a crosslinkable functional group. According to one example, the copolymer contains ethylene oxide-based units and -O-CH2-CHR units, where R is a substituent containing a radical crosslinkable functional group and is selected independently from each other unit. For example, R' is a substituent not containing a radical crosslinkable functional group and is selected independently from each other unit.

[0041] According to another example, the copolymer has a polymolecularity index (I=M w / M n )(where M n is the number average molecular weight of the copolymer, greater than or equal to 20,000; M w is the weight average molecular weight.

[0042] According to another example, the copolymer is crosslinked.

[0043] According to another example, the salt is a lithium salt. For example, the lithium salt may be lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium 2-trifluoromethyl-4,5-dicyanoimidazolate (LiTDI), lithium 4,5-dicyano-1,2,3-triazolate (LiDCTA), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiBOB), lithium nitrate (LiNO3), lithium chloride (LiCl), The lithium salt is selected from the group consisting of lithium bromide (LiBr), lithium fluoride (LiF), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiSO3CF3) (LiOTf), lithium fluoroalkylphosphate Li[PF3(CF2CF3)3] (LiFAP), lithium tetrakis(trifluoroacetoxy)borate Li[B(OCOCF3)4] (LiTFAB), lithium bis(1,2-benzenediolato(2-)-O,O')borate Li[B(CO2)2] (LiBBB), and combinations of at least two of them. According to a variant of interest, the lithium salt is LiTFSI.

[0044] In another embodiment, the coating layer has a thickness in the range of about 1 μm to about 20 μm, or about 1 μm to about 19 μm, or about 1 μm to about 18 μm, or about 1 μm to about 17 μm, or about 1 μm to about 16 μm, or about 1 μm to about 15 μm, or about 1 μm to about 14 μm, or about 1 μm to about 13 μm, or about 2 μm to about 12 μm, inclusive. According to one example, the thickness of the coating layer is in the range of about 2 μm to about 12 μm, inclusive.

[0045] In another embodiment, the electrochemically active material is lubricated.

[0046] In another embodiment, the coating layer is a first coating layer and the electrode material comprises a second coating material layer.

[0047] According to one example, the second coating layer has a thickness in the range of about 1 μm to about 20 μm, or about 1 μm to about 19 μm, or about 1 μm to about 18 μm, or about 1 μm to about 17 μm, or about 1 μm to about 16 μm, or about 1 μm to about 15 μm, or about 1 μm to about 14 μm, or about 2 μm to about 14 μm, inclusive. According to a variant of the invention, the thickness of the second coating layer is in the range of about 2 μm to about 14 μm, inclusive.

[0048] According to another example, the second coating layer includes a non-crosslinked polymer.

[0049] According to another aspect, the present technology relates to a method for preparing an electrode material as defined herein, comprising the step of depositing a coating layer based on a calcined lithiophilic organometallic structure on the surface of an electrochemically active material.

[0050] In one embodiment, the method further comprises depositing a second coating layer.

[0051] In another embodiment, the depositing step is performed by at least one of a printing method such as doctor blade coating, comma coating, reverse comma coating, gravure coating, slot die coating, or spray deposition. According to one example, the depositing step is performed by spray deposition.

[0052] In one embodiment, the method further comprises preparing a coating layer based on the calcined lithiophilic organometallic structure.

[0053] According to one example, the preparation of a coating layer based on a calcined lithiophilic organometallic structure further comprises the step of preparing a calcined lithiophilic organometallic structure, for example comprising the steps of (i) contacting at least one organic ligand with at least one lithiophilic metal precursor to obtain a lithiophilic organometallic structure, and (ii) calcining the lithiophilic organometallic structure obtained in (i) to obtain a calcined lithiophilic organometallic structure.

[0054] According to another aspect, the present technology relates to a negative electrode comprising, on a current collector, an electrode material as defined herein or obtained according to a method as defined herein.

[0055] According to another aspect, the present technology relates to a self-supporting negative electrode comprising an electrode material as defined herein or obtained according to a method as defined herein.

[0056] According to another aspect, the present technology relates to an electrochemical cell comprising a negative electrode, a positive electrode, and an electrolyte, wherein the negative electrode is as defined herein or comprises an electrode material as defined herein.

[0057] In one embodiment, the positive electrode comprises an electrochemically active material selected from a metal oxide, a metal sulfide, a metal oxysulfide, a metal phosphate, a metal fluorophosphate, a metal oxyfluorophosphate, a metal sulfate, a metal halide, a metal fluoride, sulfur, selenium, and combinations of at least two thereof.

[0058] According to one example, the metal of the electrochemically active material is selected from titanium (Ti), iron (Fe), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), chromium (Cr), copper (Cu), zirconium (Zr), niobium (Nb), and combinations of at least two thereof.

[0059] According to another example, the metal of the electrochemically active material further comprises an alkali or alkaline earth metal selected from lithium (Li), sodium (Na), potassium (K), and magnesium (Mg).

[0060] According to another example, the electrochemically active material is a lithium metal phosphate. For example, the lithium metal phosphate is LiFePO4.

[0061] In another embodiment, the electrolyte is a solid polymer electrolyte comprising a salt in a solvating polymer. According to an alternative, the electrolyte is a liquid electrolyte comprising a salt in a solvent. According to another alternative, the electrolyte is a gel electrolyte comprising a salt in a solvent and, optionally, a solvating polymer. According to one example, the salt is a lithium salt. For example, the lithium salt may be lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium 2-trifluoromethyl-4,5-dicyanoimidazolate (LiTDI), lithium 4,5-dicyano-1,2,3-triazolate (LiDCTA), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiBOB), lithium nitrate (LiNO3), lithium chloride (LiCl), The lithium salt is selected from the group consisting of lithium bromide (LiBr), lithium fluoride (LiF), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiSO3CF3) (LiOTf), lithium fluoroalkylphosphate Li[PF3(CF2CF3)3] (LiFAP), lithium tetrakis(trifluoroacetoxy)borate Li[B(OCOCF3)4] (LiTFAB), lithium bis(1,2-benzenediolato(2-)-O,O')borate Li[B(CO2)2] (LiBBB), and combinations of at least two of them. According to a variant of interest, the lithium salt is LiTFSI.

[0062] According to another aspect, the present technology relates to a battery comprising at least one electrochemical cell as defined herein.

[0063] In one embodiment, the battery is selected from the group consisting of lithium batteries, lithium ion batteries, sodium batteries, sodium ion batteries, potassium batteries, potassium ion batteries, magnesium batteries, and magnesium ion batteries. According to a variation of the object, the battery is a lithium battery. According to another variation of the object, the battery is a lithium ion battery. [Brief description of the drawings]

[0064] [Figure 1] FIG. 1 shows the thermogravimetric analysis results for (A) MOF1, (B) MOF2, (C) MOF3 (solid line) and MOF4 (dashed line), and (D) MOF5, as described in Example 1(b).

[0065] [Diagram 2] FIG. 2 shows images of MOF1 particles obtained by scanning electron microscopy (SEM) at different magnifications, as described in Example 1(c).

[0066] [Diagram 3] FIG. 3 shows images of MOF2 particles obtained by SEM at different magnifications, as described in Example 1(c).

[0067] [Figure 4] FIG. 4 shows images of MOF3 particles obtained by SEM at different magnifications, as described in Example 1(c).

[0068] [Diagram 5] FIG. 5 shows images of MOF4 particles obtained by SEM at different magnifications, as described in Example 1(c).

[0069] [Figure 6]FIG. 6 shows images of MOF5 particles obtained by SEM at different magnifications, as described in Example 1(c).

[0070] [Figure 7] FIG. 7 shows (A) an image obtained by SEM of a MOF1 particle, and (B)-(D) energy dispersive X-ray spectroscopy (EDS) mapping images of elements C, O, and Cu, respectively, as described in Example 1(d).

[0071] [Figure 8] FIG. 8 shows (A) an image obtained by SEM of a MOF2 particle, and (B)-(D) EDS mapping images of the elements Ni, C and O, respectively, as described in Example 1(d).

[0072] [Figure 9] FIG. 9 shows (A) an image obtained by SEM of MOF3, and (B)-(D) EDS mapping images of elements O, C and Zn, respectively, as described in Example 1(d).

[0073] [Figure 10] FIG. 10 shows (A) an image obtained by SEM of MOF4, and (B)-(D) EDS mapping images of elements C, O, and Zn, respectively, as described in Example 1(d).

[0074] [Figure 11] FIG. 11 shows the results of thermogravimetric analysis, as described in Example 2(b), for (A) MOF6, (B) MOF7, and (C) MOFs 8-10.

[0075] [Figure 12] FIG. 12 shows the Raman spectra obtained for MOFs 6, 7 and 10, as described in Example 2(c).

[0076] [Figure 13]FIG. 13 shows the Raman spectra obtained for MOFs 8 and 9, as described in Example 2(c).

[0077] [Figure 14] FIG. 14 shows a graph of (A) the volume of nitrogen adsorbed per gram of sample as a function of the relative pressure of nitrogen (P / P), (B) a graph of the distribution of pore volume as a function of pore width, (C) a graph of the specific surface area as a function of pore width, and (D) a graph of the total pore volume as a function of pore width obtained for MOF6, as described in Example 2(d).

[0078] [Figure 15] FIG. 15 shows a graph of (A) the volume of nitrogen adsorbed per gram of sample as a function of the relative pressure of nitrogen (P / P), (B) a graph of the distribution of pore volume as a function of pore width, (C) a graph of the specific surface area as a function of pore width, and (D) a graph of the total pore volume as a function of pore width obtained for MOF7, as described in Example 2(d).

[0079] [Figure 16] FIG. 16 shows a graph of (A) the volume of nitrogen adsorbed per gram of sample as a function of the relative pressure of nitrogen (P / P), (B) the distribution of pore volume as a function of pore width, (C) the specific surface area as a function of pore width, and (D) the total pore volume as a function of pore width obtained for MOF8 (diamonds), MOF9 (stars), and MOF10 (squares), as described in Example 2(d).

[0080] [Figure 17] FIG. 17 shows a transmission electron microscope (TEM) image of MOF6, as described in Example 2(e).

[0081] [Figure 18]FIG. 18 shows (A)-(C) TEM images of MOF6, (D) Cu EDS mapping image, and (E) a graph showing the results of EDS analysis obtained for the area defined in (D), as described in Example 2(e).

[0082] [Figure 19] FIG. 19 shows an image obtained by TEM of MOF6, as described in Example 2(e).

[0083] [Figure 20] FIG. 20 shows (A)-(C) TEM images of MOF6, (D) EDS mapping image of Cu, (E) EDS mapping images of C (red) and Cu (green), and (F) a graph showing the results of EDS analysis obtained for the areas defined in (D) and (E), as described in Example 2(e).

[0084] [Figure 21] FIG. 21 shows an image obtained by TEM of MOF6, as described in Example 2(e).

[0085] [Figure 22] FIG. 22 shows an image obtained by TEM of MOF6, as described in Example 2(e).

[0086] [Diagram 23] FIG. 23 shows (A)-(C) TEM images of MOF7, (D) Ni EDS mapping image, and (E) and (F) graphs showing the results of EDS analysis obtained for the area defined in (D), as described in Example 2(e).

[0087] [Figure 24] FIG. 24 shows an image obtained by TEM of MOF7, as described in Example 2(e).

[0088] [Diagram 25]FIG. 25 shows an image obtained by TEM of MOF7, as described in Example 2(e).

[0089] [Figure 26] FIG. 26 shows (A) and (B) images obtained by TEM of MOF10, and (C) the results of the corresponding EDS analysis, as described in Example 2(e).

[0090] [Figure 27] FIG. 27 shows (A) and (B) images obtained by TEM of MOF10, and (C) an EDS mapping image of Zn, as described in Example 2(e).

[0091] [Figure 28] FIG. 28 shows (A) an image obtained by TEM of MOF10, (B) an EDS mapping image of Zn, and (C) a graph showing the results of EDS analysis obtained for the area defined in (B), as described in Example 2(e).

[0092] [Figure 29] FIG. 29 shows (A) an image obtained by TEM of MOF9, (B)-(E) EDS mapping images of Zn, C, O and Si, respectively, as well as (F) the corresponding EDS analysis results obtained for the two regions defined in (A)-(E), as described in Example 2(e).

[0093] [Diagram 30] FIG. 30 shows (A)-(C) images obtained by TEM of MOF9, (D)-(G) EDS mapping images of Zn, O, C and Si, respectively, as described in Example 2(e), and (H) the corresponding EDS analysis results obtained for the two regions defined in (C)-(G).

[0094] [Diagram 31]FIG. 31 shows (A) and (B) images obtained by TEM of MOF9, as described in Example 2(e), and (C)-(F) corresponding EDS analysis results obtained for the two regions indicated by the arrows in (B).

[0095] [Diagram 32] FIG. 32 shows an image obtained by TEM of MOF9, as described in Example 2(e).

[0096] [Diagram 33] FIG. 33 shows an image obtained by TEM of MOF8, as described in Example 2(e).

[0097] [Diagram 34] FIG. 34 shows (A) an image obtained by TEM of MOF8, (B)-(D) EDS mapping images of Zn, C and O, respectively, as well as (E) the corresponding EDS analysis results obtained for the regions defined in (A)-(D), as described in Example 2(e).

[0098] [Diagram 35] FIG. 35 shows (A)-(C) images obtained by TEM of MOF8, (D)-(F) EDS mapping images of Zn, C, and O, respectively, as described in Example 2(e), and (G) the corresponding EDS analysis results obtained for the regions defined in (C)-(F).

[0099] [Diagram 36] FIG. 36 shows (A) and (C) images obtained by TEM of MOF8, as described in Example 2(e), and (D) the results of an EDS analysis obtained for the two regions indicated by the arrows in the corresponding TEM image also shown in (D).

[0100] [Figure 37]FIG. 37 shows (A) an image obtained by TEM of MOF8, (B)-(D) EDS mapping images of Zn, C and O, respectively, and (E) and (F) the corresponding EDS analysis results obtained for regions 1 and 2 defined in (A)-(D), respectively, as described in Example 2(e).

[0101] [Figure 38] FIG. 38 shows an image obtained by TEM of MOF8, as described in Example 2(e).

[0102] [Figure 39] FIG. 39 shows images obtained by SEM of MOF8 (A) before grinding, (B) after grinding for about 5 minutes, and (C) after grinding twice for about 5 minutes, as described in Example 2(f).

[0103] [Diagram 40] FIG. 40 shows (A) an image obtained by TEM of MOF8 after two grindings for about 5 min, and (B) and (C) EDS mapping images of C and Zn, respectively, as described in Example 2(f).

[0104] [Diagram 41] FIG. 41 shows the thermogravimetric analysis results for (A) MOF11, (B) MOF12, (C) MOF13, (D) MOF14, and (E) MOF15, as described in Example 3(b).

[0105] [Diagram 42] FIG. 42 shows an image obtained by SEM of MOF11, as described in Example 3(c).

[0106] [Diagram 43] FIG. 43 shows an image obtained by SEM of MOF12, as described in Example 3(c).

[0107] [Diagram 44] FIG. 44 shows an image obtained by SEM of MOF13, as described in Example 3(c).

[0108] [Diagram 45] FIG. 45 shows an image obtained by SEM of MOF14, as described in Example 3(c).

[0109] [Diagram 46] FIG. 46 shows an image obtained by SEM of MOF15, as described in Example 3(c).

[0110] [Figure 47] FIG. 47 shows (A) an image obtained by SEM of MOF11, and (B)-(E) EDS mapping images of C, Zn, Cu and O, respectively, as described in Example 3(d).

[0111] [Figure 48] FIG. 48 shows (A) an image obtained by SEM of MOF11, and (B)-(E) EDS mapping images of Zn, C, O, and Cu, respectively, as described in Example 3(d).

[0112] [Figure 49] FIG. 49 shows (A) an image obtained by SEM of MOF13, and (B)-(E) EDS mapping images of Zn, C, O, and Cu, respectively, as described in Example 3(d).

[0113] [Figure 50] FIG. 50 shows (A) an image obtained by SEM of MOF14, and (B)-(E) EDS mapping images of C, O, Cu and Zn, respectively, as described in Example 3(d).

[0114] [Figure 51]FIG. 51 shows (A) an image obtained by SEM of MOF15, and (B)-(E) EDS mapping images of Zn, C, O, and Cu, respectively, as described in Example 3(d).

[0115] [Figure 52] FIG. 52 shows the thermogravimetric analysis results for (A) MOF11, (B) MOF12, and (C) MOF13, as described in Example 3(e).

[0116] [Figure 53] FIG. 53 shows (A) and (B) images obtained by SEM of MOFs that have been calcined at a temperature of about 1000° C. and ground, as described in Example 3(f), and (C) the results of the corresponding EDS analysis.

[0117] [Figure 54] FIG. 54 shows the thermogravimetric analysis results for (A) MOF16, (B) MOF17, (C) MOF18, and (D) MOF19, as described in Example 4(b).

[0118] [Figure 55] FIG. 55 shows (A) nitrogen adsorption / desorption isotherms, (B) a graph of the distribution of pore volume as a function of pore width, (C) a graph of the specific surface area as a function of pore width, and (D) a graph of the total pore volume as a function of pore width obtained for MOFs 16 (squares), 17 (triangles), 18 (circles), and 19 (stars), as described in Example 4(c).

[0119] [Figure 56] FIG. 56 shows an image obtained by SEM of MOF16, as described in Example 4(d).

[0120] [Figure 57] FIG. 57 shows an image obtained by SEM of MOF17, as described in Example 4(d).

[0121] [Figure 58] FIG. 58 shows an image obtained by SEM of MOF18, as described in Example 4(d).

[0122] [Figure 59] FIG. 59 shows an image obtained by SEM of MOF19, as described in Example 4(d).

[0123] [Figure 60] FIG. 60 shows (A) an SEM image obtained for MOF16, (B) a graph showing the results of an EDS analysis obtained for the area defined in (A), as described in Example 4(e).

[0124] [Figure 61] FIG. 61 shows (A) an image obtained by SEM of MOF17, and (B)-(E) EDS mapping images of C, Ag, O, and Zn, respectively, as described in Example 4(e).

[0125] [Figure 62] FIG. 62 shows (A) an image obtained by SEM of MOF18, and (B)-(E) EDS mapping images of C, O, Ag, and Zn, respectively, as described in Example 4(e).

[0126] [Figure 63] FIG. 63 shows the thermogravimetric analysis results for (A) MOF20 and (B) MOF21, as described in Example 5(b).

[0127] [Figure 64] FIG. 64 shows an image obtained by SEM of MOF20, as described in Example 5(c).

[0128] [Figure 65]FIG. 65 shows images obtained by SEM of MOF21 before and after calcination at a temperature of about 750° C., as described in Example 5(c).

[0129] [Figure 66] FIG. 66 shows images obtained by SEM of MOF22 before and after calcination at a temperature of about 1000° C., as described in Example 5(c).

[0130] [Figure 67] FIG. 67 shows (A) an image obtained by SEM of MOF21 before calcination, and (B)-(E) EDS mapping images of O, Mg, C, and Zn, respectively, as described in Example 5(d).

[0131] [Figure 68] FIG. 68 shows (A) an image obtained by SEM of MOF21 after calcination at a temperature of about 750° C., (B)-(E) EDS mapping images of Zn, Mg, C, and O, respectively, and (F) the corresponding EDS analysis results, as described in Example 5(d).

[0132] [Figure 69] FIG. 69 shows (A) an image obtained by SEM of MOF22 before calcination, and (B)-(F) EDS mapping images of C, O, Ir, Zn, and Mg, respectively, as described in Example 5(d).

[0133] [Figure 70] FIG. 70 shows (A) an image obtained by SEM of MOF22 after calcination at a temperature of about 1000° C., (B)-(E) EDS mapping images of C, O, Mg, and Zn, respectively, and (F) the corresponding EDS analysis results, as described in Example 5(d).

[0134] [Figure 71] FIG. 71 shows an image obtained by SEM of MOF23, as described in Example 6(b).

[0135] [Figure 72] FIG. 72 shows an image obtained by SEM of MOF24, as described in Example 6(b).

[0136] [Figure 73] FIG. 73 shows (A) an image obtained by TEM of MOF23, (B)-(D) EDS mapping images of C, O, and Mg, respectively, and (E) the results of the corresponding EDS analysis, as described in Example 6(c).

[0137] [Figure 74] FIG. 74 shows (A) an image obtained by TEM of MOF24, (B)-(D) EDS mapping images of C, O, and Mg, respectively, and (E) the results of the corresponding EDS analysis, as described in Example 6(c).

[0138] [Figure 75] FIG. 75 shows an image obtained by SEM of MOF25, as described in Example 7(b).

[0139] [Figure 76] FIG. 76 shows an image obtained by SEM of MOF26, as described in Example 7(b).

[0140] [Figure 77] FIG. 77 shows an image obtained by SEM of MOF27, as described in Example 7(b).

[0141] [Figure 78] FIG. 78 shows an image obtained by SEM of MOF28, as described in Example 7(b).

[0142] [Figure 79] FIG. 79 shows an image obtained by SEM of MOF29, as described in Example 7(b).

[0143] [Figure 80] FIG. 80 shows an image obtained by SEM of MOF30, as described in Example 7(b).

[0144] [Figure 81] FIG. 81 shows (A) an image obtained by SEM of MOF25, and (B)-(D) EDS mapping images of C, O, and Sb, respectively, as described in Example 7(c).

[0145] [Figure 82] FIG. 82 shows (A) an image obtained by SEM of MOF26, and (B)-(E) EDS mapping images of C, O, Zn, and Sb, respectively, as described in Example 7(c).

[0146] [Figure 83] FIG. 83 shows (A) an image obtained by SEM of MOF27, and (B)-(E) EDS mapping images of C, O, Zn, and Sb, respectively, as described in Example 7(c).

[0147] [Figure 84] FIG. 84 shows (A) an image obtained by SEM of MOF28, and (B)-(E) EDS mapping images of C, O, Zn, and Sb, respectively, as described in Example 7(c).

[0148] [Figure 85] FIG. 85 shows (A) an image obtained by SEM of MOF29, and (B)-(E) EDS mapping images of C, O, Sb, and Zn, respectively, as described in Example 7(c).

[0149] [Figure 86] FIG. 86 shows (A) an image obtained by SEM of MOF30, and (B)-(E) EDS mapping images of C, O, Sb, and Zn, respectively, as described in Example 7(c).

[0150] [Figure 87] FIG. 87 shows an image obtained by SEM of MOF31, as described in Example 8(b).

[0151] [Figure 88] FIG. 88 shows an image obtained by SEM of MOF32 before calcination, as described in Example 8(b).

[0152] [Figure 89] FIG. 89 shows an image obtained by SEM of MOF32 after calcination at a temperature of about 1000° C., as described in Example 8(b).

[0153] [Figure 90] FIG. 90 shows (A) an image obtained by SEM of MOF31, and (B)-(E) EDS mapping images of Ag, Zn, N, and O, respectively, as described in Example 8(c).

[0154] [Figure 91] FIG. 91 shows (A) an image obtained by SEM of MOF32 before calcination, and (B)-(E) EDS mapping images of Zn, Ag, N, and O, respectively, as described in Example 8(c).

[0155] [Figure 92] FIG. 92 shows (A) an image obtained by SEM of MOF32 after calcination at a temperature of about 1000° C., as described in Example 8(c), and EDS mapping of C (red) and Ag (green), as well as (B) and (C) EDS mapping images of Ag and C, respectively, obtained for the area defined in (A).

[0156] [Figure 93]FIG. 93 shows the results of EDS analysis for MOF32 after calcination at a temperature of about 1000° C., as described in Example 8(c), obtained for (A) the total spectrum, (B) spectrum 14, and (C) spectrum 15.

[0157] [Figure 94] FIG. 94 shows a graph of capacity versus cycle number obtained at charge / discharge currents of C / 6, C / 4, C / 3, C / 2 and 1C for cells 8 (triangles) and 9 (inverted triangles), and references 3 (squares) and 4 (circles), as described in Example 9(c).

[0158] [Figure 95] FIG. 95 shows an image obtained by SEM of Layer 1, as described in Example 10(b).

[0159] [Figure 96] FIG. 96 shows an image obtained by SEM of Layer 2, as described in Example 10(b).

[0160] [Figure 97] FIG. 97 shows (A) an SEM image and EDS mapping of Zn (blue), Cu (green), and Al (red) obtained for layer 1, as described in Example 10(c), and (B) and (C) EDS mapping images of Cu and Zn, respectively, obtained for the area defined in (A).

[0161] [Figure 98] FIG. 98 shows (A) an SEM image obtained for layer 2, (B) an SEM image obtained for layer 2 and EDS mapping of Cu (pink), Al (blue), O (green), and C (red), and (C) and (D) EDS mapping images of Cu and C obtained for the areas defined in (A) and (B), respectively, as described in Example 10(c).

[0162] [Figure 99]FIG. 99 shows (A) an SEM image and EDS mapping of O (green) and C (red) obtained for layer 2, as described in Example 10(c), and (B) and (C) EDS mapping images of C and O, respectively, obtained for the area defined in (A).

[0163] [Figure 100] FIG. 100 shows a graph of capacity versus cycle number obtained at charge / discharge currents of C / 6, C / 4, C / 3, C / 2 and 1C for cells 10 (square), 11 (circle), 12 (triangle) and 13 (inverted triangle), and references 5 (star) and 6 (hexagon), as described in Example 10(d).

[0164] [Figure 101] FIG. 101 shows a graph of the coulombic efficiency versus cycle number obtained for cells 10 (square), 11 (circle), 12 (triangle) and 13 (inverted triangle), as well as references 5 (star) and 6 (hexagon), as described in Example 10(d). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0165] Detailed Description All scientific and technical terms and expressions used herein have the same definitions as commonly understood by those skilled in the art. Nevertheless, definitions of some of the terms and expressions used are provided below.

[0166] When the term "about" is used herein, it means approximately, within a range, or approximately.For example, when the term "about" is used in relation to a numerical value, it modifies the numerical value by a variation of 10% above or below the numerical value.This term can also take into account, for example, experimental error or rounding of a measuring device.

[0167] When a range of values ​​is mentioned in this application, the lower and upper limits of the range are always included in this definition, unless otherwise indicated. When a range of values ​​is mentioned in this application, all intermediate ranges and subranges, as well as individual values, contained within the range of values ​​are included in this definition.

[0168] When the article "a" is used to introduce elements of this application, it does not have the meaning of "only one," but rather the meaning of "one or more." Of course, when the description states that a particular step, component, element, or feature "may" be included or "can be included," it does not require that the particular step, component, element, or feature be included in every embodiment.

[0169] The term "self-supporting electrode," as used herein, refers to an electrode that does not include a metal current collector.

[0170] The chemical structures described herein are drawn according to the conventions of the art. Also, when a depicted atom, such as a carbon atom, appears to contain incomplete valences, it is assumed that the valences are satisfied by one or more hydrogen atoms, even if not explicitly depicted.

[0171] The term "aromatic" refers to a monocyclic group having a total of 6 to 15 ring members, where at least one of the rings in the system is aromatic, or a fused bicyclic or tricyclic system having 4n+2 conjugated π (pi) electrons, where n is a number from 1 to 3.

[0172] The present technology relates to the formation of a layer of a coating material on an electrode material that includes an electrochemically active material. The coating material includes a metal-organic structure ("metal-organic framework, MOF") that forms a network of at least one lithiophilic metal and at least one organic ligand. The metal-organic structure of the coating is preferably calcined before its application to the electrode film. The electrode is preferably a negative electrode.

[0173] The present technology thus relates to an electrode material comprising an electrochemically active material and a coating layer comprising a coating material based on a calcined lithiophilic organometallic structure comprising at least one lithiophilic metal and at least one at least partially calcined organic ligand, said coating layer being disposed on a surface of said electrochemically active material.

[0174] The electrochemically active material may comprise an alkali metal, an alkaline earth metal, a non-alkaline and non-alkaline earth metal, or an alloy comprising at least one of them, for example in the form of a metal film. Preferably, the electrochemically active material comprises an alkali metal, an alkaline earth metal, or an alloy comprising at least one alkali or alkaline earth metal. For example, the electrochemically active material comprises metallic lithium, or an alloy comprising or based on metallic lithium. The electrochemically active material may also comprise nickel. According to one example, the electrochemically active material is a lubricated metal film.

[0175] When the electrochemically active material is in the form of a film, it may have a thickness in the range of about 5 μm to about 75 μm, or about 15 μm to about 70 μm, or about 25 μm to about 65 μm, or about 30 μm to about 60 μm, or about 45 μm to about 55 μm, including upper and lower limits.

[0176] The organometallic structure includes a lithiophilic metal. Any known compatible lithiophilic metal is contemplated. Non-limiting examples of lithiophilic metals include Ag, Zn, Sn, Sb, Mg, Al, Ni, Cu, Co, and combinations of at least two of them. After calcination, the lithiophilic metal may be present in the calcined lithiophilic organometallic structure, for example, in elemental, metal oxide, metal nitride, and / or metal fluoride form. For example, the form in which the lithiophilic metal is present in the calcined lithiophilic organometallic structure may vary depending on the gas or mixture of gases present in the atmosphere used during calcination of the lithiophilic organometallic structure.

[0177] The organic ligand before calcination is generally an organic compound that includes at least two functional groups capable of forming a bond (e.g., ionic bond, covalent bond, etc.) with the lithiophilic metal. Each of these functional groups generally includes at least one heteroatom (e.g., N, O, S, P, etc.). For example, the organic ligand is an organic ligand that includes a nitrogen functional group, an organic ligand that includes a carboxylate, or a mixed organic ligand that includes nitrogen and / or carboxylate functional groups. For example, the ligand includes at least two, or at least three, or at least four carboxylate groups (e.g., 1,2,4,5-benzenetetracarboxylic acid), preferably linked by an aromatic or polyaromatic group. Alternatively, the ligand includes at least one carboxylate group and a nitrogen functional group (e.g., 1H-benzimidazole-6-carboxylic acid) that are linked by or form part of an aromatic group. Any type of compatible organic ligand that forms a repeating structure with the lithiophilic metal is contemplated.

[0178] Non-limiting examples of lithiophilic organometallic structures (before calcination) include formulas 1-9, or one of their positional isomers: [ka] [ka] [ka] (wherein n1 and n2, if present, represent the ratio of each unit and are independently selected numbers ranging from 0.1 to 0.9).

[0179] Some of the calcined lithiophilic organometallic structures may also further include a metal source, such as a silver source. According to one example, the silver source is a silver salt, such as silver chloride (AgCl) or silver nitrate (AgNO3). When a silver salt is included, it may be present in a lithiophilic metal:silver ratio ranging from about 1:1 to about 5:1, or from about 4:3 to about 4:1, including upper and lower limits.

[0180] The coating material may also contain other elements such as a solid electrolyte polymer, preferably crosslinked. The latter may be composed of a salt in a solvating polymer. The solid electrolyte polymer contained in the coating material may thus be a copolymer of ethylene oxide and at least one substituted oxirane containing a crosslinkable functional group.

[0181] According to one example, the copolymer comprises ethylene oxide-based units and -O-CH2-CHR units, where R is a substituent that comprises a crosslinkable functional group, for example via a radical pathway, and is selected independently for each unit. The copolymer may also further comprise -O-CH2-CHR'- units, where R' is a substituent that does not comprise a radical crosslinkable functional group, and is selected independently for each unit.

[0182] In some examples, the copolymers have a polymolecularity index (I=M w / M n )(where M n is the number average molecular weight of the copolymer, greater than or equal to 20,000; M w where m is the weight average molecular weight. For example, the polymolecularity index can be determined by size exclusion chromatography (SEC).

[0183] The salt contained in the solid polymer electrolyte of the coating material is preferably a lithium salt. Non-limiting examples of lithium salts include lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium 2-trifluoromethyl-4,5-dicyanoimidazolate (LiTDI), lithium 4,5-dicyano-1,2,3-triazolate (LiDCTA), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiBOB), lithium nitrate (LiNO3), lithium chloride (Li iCl), lithium bromide (LiBr), lithium fluoride (LiF), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiSO3CF3) (LiOTf), lithium fluoroalkylphosphate Li[PF3(CF2CF3)3] (LiFAP), lithium tetrakis(trifluoroacetoxy)borate Li[B(OCOCF3)4] (LiTFAB), lithium bis(1,2-benzenediolato(2-)-O,O')borate Li[B(CO2)2] (LiBBB), or a combination of at least two thereof. Preferably, the lithium salt comprises LiTFSI.

[0184] The coating layer may have a thickness in the range of about 1 μm to about 20 μm, or about 1 μm to about 19 μm, or about 1 μm to about 18 μm, or about 1 μm to about 17 μm, or about 1 μm to about 16 μm, or about 1 μm to about 15 μm, or about 1 μm to about 14 μm, or about 1 μm to about 13 μm, or about 2 μm to about 12 μm, inclusive, preferably about 2 μm to about 12 μm, inclusive.

[0185] According to another example, the coating layer is a first coating layer, and the electrode material comprises a second layer of coating material. For example, the second coating layer may have a thickness in the range of about 1 μm to about 20 μm, inclusive, or about 1 μm to about 19 μm, or about 1 μm to about 18 μm, or about 1 μm to about 17 μm, or about 1 μm to about 16 μm, or about 1 μm to about 15 μm, or about 1 μm to about 14 μm, or about 2 μm to about 14 μm, inclusive, preferably in the range of about 2 μm to about 14 μm, inclusive. Preferably, the second coating layer comprises a polymer, such as a non-crosslinked solid electrolyte polymer.

[0186] The electrode material as defined herein is generally prepared by a method comprising the step of depositing a coating layer based on a calcined lithiophilic organometallic structure on the surface of an electrochemically active material. According to some examples, the method further comprises the step of depositing a second coating layer. The depositing step(s) may be carried out by at least one of a printing method such as doctor blade coating, comma coating, reverse comma coating, gravure coating, slot die coating, or spray deposition. Preferably, the depositing step(s) is carried out by spray deposition.

[0187] The method may also further include preparing a coating material based on the calcined lithiophilic organometallic structure, including, for example, preparing a calcined lithiophilic organometallic structure. For example, preparing the calcined lithiophilic organometallic structure includes contacting at least one organic ligand with at least one lithiophilic metal precursor to obtain a lithiophilic organometallic structure, and calcining the lithiophilic organometallic structure to obtain a calcined lithiophilic organometallic structure. For example, the calcination step is carried out at a temperature in the range of about 500°C to about 1050°C, inclusive, preferably in the range of about 550°C to about 1000°C, inclusive. The calcination step may be carried out in an inert atmosphere, including, for example, a gas selected from argon, nitrogen, helium, fluorinated gas, and a mixture including at least one of them. Preferably, the inert atmosphere gas includes argon.

[0188] The electrode material is used in the manufacture of an electrode, for example a negative electrode. For example, a negative electrode as contemplated herein includes an electrode material as defined herein, with or without a current collector (self-supporting), or an electrode material obtained according to the method defined above.

[0189] Also contemplated are electrochemical cells comprising the electrode material or the negative electrode described above, for example comprising a negative electrode, a positive electrode, and an electrolyte, where the negative electrode is as defined above or comprises an electrode material as defined herein.

[0190] The positive electrode includes an electrochemically active material. Examples of the electrochemically active material of the positive electrode include metal oxides, metal sulfides, metal oxysulfides, metal phosphates, metal fluorophosphates, metal oxyfluorophosphates, metal sulfates, metal halides, metal fluorides, sulfur, selenium, and, where appropriate, combinations of at least two of them. For example, the metal of the electrochemically active material is selected from titanium (Ti), iron (Fe), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), chromium (Cr), copper (Cu), zirconium (Zr), niobium (Nb), and combinations of at least two of them. The metal may further include an alkali or alkaline earth metal selected from lithium (Li), sodium (Na), potassium (K), and magnesium (Mg). According to one example, the electrochemically active material of the positive electrode is a lithium metal phosphate, such as LiFePO4.

[0191] The electrolyte of the electrochemical cell is preferably a solid electrolyte, for example a solid polymer electrolyte comprising a salt in a solvating polymer, which may be as defined for the coating material.

[0192] This document also relates to an electrochemical accumulator or battery comprising at least one electrochemical cell as defined herein, for example the battery is selected from the group consisting of lithium batteries, lithium ion batteries, sodium batteries, sodium ion batteries, potassium batteries, potassium ion batteries, magnesium batteries and magnesium ion batteries, preferably lithium or lithium ion batteries.

[0193] The present technology also includes the use of the present electrochemical accumulators or batteries in portable devices (e.g., mobile phones, cameras, tablets or laptops), electric or hybrid vehicles, or renewable energy storage, among others. EXAMPLES

[0194] The following examples are for illustrative purposes only and should not be construed as further limiting the scope of the invention as contemplated. These examples are better understood with reference to the accompanying drawings.

[0195] Example 1 Preparation and characterization of lithiophilic MOFs based on metal cations coupled with aromatic polycarboxylate ligands

[0196] a) Preparation of lithiophilic MOF

[0197] Metal cation (M=Cu 2+ , Ni 2+ , Zn 2+ , or Co 2+ Lithiophilic MOFs based on H4btec were prepared from 1,2,4,5-benzenetetracarboxylic acid (H4btec) and at least one metal salt or compound (e.g., copper(II) acetate (Cu(OAc)2), nickel(II) carbonate (NiCO3), zinc oxide (ZnO), or cobalt(II) carbonate (CoCO3)). The MOFs prepared in this example are shown in Table 1. [Table 1]

[0198] b) Characterization of lithiophilic MOFs by thermogravimetric analysis (TGA)

[0199] The MOFs prepared in Example 1(a) were characterized by thermogravimetric analysis to evaluate their thermal stability and their transformation process. Thermogravimetric analysis was carried out over a temperature range of about 30° C. to about 1000° C. under a constant air flow rate of 100 mL / min and a heating rate of 5° C. / min. The thermogravimetric analysis results obtained for MOFs 1-5 are shown in FIG. 1 and summarized in Table 2. [Table 2]

[0200] FIG. 1(A) shows a first mass loss that can be attributed to the removal of water at temperatures below 100° C., a second mass loss that can be attributed to the decomposition of coordinated water molecules from a temperature of about 150° C., and a third mass loss that can be attributed to the decomposition of organic ligands starting at a temperature of about 250° C.

[0201] FIG. 1(B) shows a first mass loss that can be attributed to the removal of water at temperatures below 150° C., and a second mass loss that can be attributed to the decomposition of the organic ligands starting at a temperature of about 360° C.

[0202] FIG. 1(C) shows a first mass loss that can be attributed to the removal of water at temperatures below 100° C., and a second mass loss that can be attributed to the decomposition of the organic ligands starting at a temperature of about 450° C.

[0203] FIG. 1(D) shows a first mass loss that can be attributed to the removal of water at temperatures below 250° C., and a second mass loss that can be attributed to the decomposition of the organic ligands starting at a temperature of about 350° C.

[0204] c) SEM characterization of lithiophilic MOFs

[0205] The MOFs prepared in Example 1(a) were imaged using a scanning electron microscope (SEM) equipped with a secondary electron (SE) detector to highlight topography and morphology, and a backscattered electron (BSE) detector to study chemical contrast, or only a BSE detector where indicated. All SEM images were obtained at an accelerating voltage of 10.0 kV. The images obtained for MOFs 1-5 are shown in Figures 2-6 and summarized in Table 3. [Table 3]

[0206] In Figures 2 and 3, it can be observed that the particles of MOFs 1 and 2 have a substantially elongated rod-like morphology with diameters ranging from about 2 µm to about 30 µm.

[0207] Figures 4 and 5 show that particles of MOFs 3 and 4 have various morphologies with diameters ranging from about 20 μm to about 200 μm, including the upper and lower limits.

[0208] Figure 6 shows SEM images obtained using (A) the SE and BSE detectors, and (B) the BSE detector. It can be observed that the MOF5 particles have various morphologies with diameters ranging from about 20 μm to about 100 μm.

[0209] d) EDS characterization of lithiophilic MOFs

[0210] Elemental analysis or chemical characterization of the MOFs prepared in Example 1(a) was carried out using a SEM equipped with an X-ray detector for EDS analysis. Figures 7-10 show (A) elemental SEM images and (B)-(D) corresponding EDS mapping images for MOFs 1-4, respectively. The images obtained from EDS mapping are summarized in Table 4. [Table 4]

[0211] The EDS mapping images in Figures 7-10 show that the particle compositions of MOFs 1-4 are essentially homogeneous at the elemental level.

[0212] Example 2 Preparation and characterization of calcined lithiophilic MOFs based on metal cations coupled with aromatic polycarboxylate ligands

[0213] a) Preparation of calcined lithiophilic MOF

[0214] The calcined MOFs based on metal cations bound to aromatic polycarboxylate ligands were prepared by adding metal cations (M = Cu 2+ , Ni 2+ , Zn 2+ Or Co 2+), and 1,2,4,5-benzenetetracarboxylic acid (H4btec). The MOFs were calcined under an inert argon atmosphere according to the following protocol: 1. Ramp from room temperature to 200°C at a rate of 1°C / min; 2. Plateau at 200℃ for 1 hour; 3. Ramp from 200°C to the calcination temperature at a rate of 3°C / min; and 4. Plateau at calcination temperature for 2 hours.

[0215] The calcined MOFs prepared in this example, the calcination temperature, the theoretical yield after calcination determined by TGA, and the yield after calcination are shown in Table 5. [Table 5]

[0216] b) Characterization of calcined lithiophilic MOFs by TGA

[0217] The calcined MOFs prepared in Example 2(a) were characterized by TGA to assess their respective metal content. Thermogravimetric analysis was carried out under a constant air flow rate of 100 mL / min and a heating rate of 5° C. / min. The thermogravimetric analysis results obtained for MOFs 6-10 are shown in FIG. 11 and summarized in Table 6. [Table 6]

[0218] Figure 11(A) shows the thermogravimetric curve obtained for MOF6. Thermogravimetric analysis was carried out over a temperature range from about 30 °C to about 700 °C. It can be observed that the oxidation mechanism of metals in air does not allow its proper quantification.

[0219] Figure 11(B) shows the thermogravimetric curve obtained for MOF 7. Thermogravimetric analysis was carried out over a temperature range from about 30 °C to about 900 °C. It can be observed that the oxidation mechanism of metals in air does not allow its proper quantification.

[0220] FIG. 11(C) shows the thermogravimetric curves obtained for MOFs 8-10. Thermogravimetric analysis was performed over a temperature range from about 50° C. to about 800° C. The mass of metal present in MOFs 8-10 was estimated to be about 70% by weight. In FIG. 11(C) it can be observed that the carbon in the MOFs calcined at higher temperatures appears graphitic and requires higher temperatures to decompose in air. In FIG. 11(C) it can also be observed that there is no mass increase, which can be due, for example, to either the presence of ZnO particles or the presence of a ZnO layer on the surface of the Zn particles.

[0221] c) Characterization of calcined lithiophilic MOFs by Raman microspectroscopy

[0222] Analysis of the molecular composition of the calcined MOF prepared in Example 2(a) was carried out by Raman microspectroscopy.

[0223] FIG. 12 shows the Raman spectra obtained for MOFs calcined at a temperature of 750° C. (MOFs 6, 7 and 10). 2+ Substantially graphitic carbon can be observed for the calcined MOF based on Cu (MOF7). 2+ and Zn 2+ Calcined MOFs based on α- and β-carbamate (MOFs 6 and 10) appear to produce carbons of similar substantially disordered nature.

[0224] FIG. 13 shows the ZnO melting point at 550° C. and 650° C. 2+ FIG. 13 shows the Raman spectra obtained for the MOFs based on MOFs (MOFs 8 and 9). (A) The intensity ratio of the D band to the G band (I D / I G) is shown. Therefore, the carbon produced by calcination of these two MOFs is considered to be substantially amorphous. Comparison of the Raman spectrum shown in Figure 13(B) with that of other Raman spectroscopy studies performed on ZnO (Song, Yin, et al. "Raman spectra and microstructure of zinc oxide irradiated with swift heavy ion." Crystals 9.8 (2019): 395) highlights the presence of ZnO in the analyzed sample.

[0225] d) Surface characterization of calcined lithiophilic MOFs by the Brunauer-Emmett-Teller (BET) method

[0226] The pore size, specific surface area, and pore volume of the calcined MOF prepared in Example 2(a) were characterized.

[0227] Nitrogen adsorption / desorption isotherm (volume of adsorbed nitrogen (cm) as a function of relative nitrogen pressure P / P0) 3 A graph of the pore size (nm), pore volume distribution (dV / dw) (cm 3 / g.nm), specific surface area (m 2 / g), and total pore volume (cm 3 The specific surface area and pore volume were calculated using the BET method.

[0228] 14 and 15 show (A) nitrogen adsorption / desorption isotherms, (B) graphs of the distribution of pore volume as a function of pore width, (C) graphs of the specific surface area as a function of pore width, and (D) graphs of the total pore volume as a function of pore width, obtained for MOFs 6 and 7, respectively.

[0229] FIG. 16 shows (A) nitrogen adsorption / desorption isotherms, (B) graphs of the distribution of pore volume as a function of pore width, (C) graphs of the specific surface area as a function of pore width, and (D) graphs of the total pore volume as a function of pore width obtained for MOF8 (diamonds), MOF9 (stars), and MOF10 (squares).

[0230] The presence of hysteresis loop characteristic of mesoporous materials can be observed in the nitrogen adsorption / desorption isotherms of each of the calcined MOFs (MOF6-10).

[0231] Furthermore, it can be concluded that a substantial portion of the specific surface area and porosity of each of the calcined MOFs (MOFs 6-10) comes from mesopores and not from micropores.

[0232] e) Surface characterization of calcined lithiophilic MOFs by TEM and EDS

[0233] The calcined MOF prepared in Example 2(a) was characterized by TEM and EDS.

[0234] 17 to 38 show the TEM images, EDS mapping images and EDS analysis results obtained for MOFs 6 to 10. The experimental conditions used for the TEM and TEM-EDS analyses performed on MOFs 6 to 10 are shown in Table 7. [Table 7-1] [Table 7-2]

[0235] Analysis of TEM and TEM-EDS images obtained for MOF6

[0236] Figure 17 shows nanometric metal particles dispersed substantially within and on the surface of the carbon. The arrows in Figures 17(B) and 17(C) each point to a copper particle.

[0237] Figure 18(E) shows the results of an EDS analysis obtained for the area defined in the EDS mapping image shown in Figure 18(D). Figure 18(E) shows the presence of copper in MOF6 and its approximate relative abundance.

[0238] FIG. 20(F) shows the results of EDS analysis obtained for the area defined in the EDS mapping images shown in FIGS. 18(D) and (E).

[0239] Figures 21 and 22 show that the carbon is substantially amorphous and substantially disordered, which is consistent with the Raman microspectroscopic analysis shown in Example 2(c).

[0240] Analysis of TEM and TEM-EDS images obtained for MOF7

[0241] Figures 23(E) and (F) show graphs of intensity (counts / sec) as a function of energy (keV) and electron count as a function of energy (eV), respectively, obtained for the region defined in the EDS mapping image shown in Figure 23(D). Figures 23(E) and (F) show the presence of copper and nickel and their approximate relative abundances.

[0242] Figure 24 shows a TEM image of MOF7, where nanometric metal particles can be observed substantially dispersed in the carbon matrix. Each line in Figure 24 represents a nickel particle.

[0243] Figure 25 shows two TEM images of MOF7, where substantially more graphitic carbon can be observed, which is consistent with the Raman microspectroscopy analysis shown in Example 2(c). Carbon planes can also be seen in this figure.

[0244] Analysis of TEM and TEM-EDS images obtained for MOF10

[0245] Figure 26 shows (A) and (B) TEM images of MOF10 and (C) the corresponding EDS analysis results. The two arrows in Figure 26(B) each point to a zinc particle. Figure 26 shows that MOF10 is substantially heterogeneous, with only a few nanometer metal particles here and there.

[0246] FIG. 28(C) is a graph showing the results of EDS analysis obtained for the area defined in the EDS mapping image shown in FIG. 28(B).

[0247] Figures 27 and 28 show the presence of zinc-containing aggregates on the surface and within the carbon matrix. These aggregates form substantially at high temperatures. Thus, some of the porosity can be attributed to zinc loss. Indeed, at 560 m for MOF10, 2 The specific surface area in g / g was obtained by BET.

[0248] Analysis of TEM and TEM-EDS images obtained for MOF9

[0249] Figure 29(F) shows the results of EDS analysis obtained for the two regions defined in the images shown in Figures 29(A)-(E). The image in Figure 29 shows the presence of elongated grains of irregular shape. The presence of silicon can also be observed in the carbon-rich region.

[0250] FIG. 30 (H) shows the results of EDS analysis obtained for the two regions defined in the images shown in FIGS. 30(C)-(G).

[0251] FIG. 31 shows (A) and (B) images obtained by TEM of MOF9, and (C)-(F) the corresponding EDS analysis results obtained for the two regions indicated by the arrows in (B). FIG. 31(C) and (D) show the graphs of intensity as a function of energy and the graphs of the number of electrons as a function of energy, respectively, obtained for the Sp75 region indicated in (B). FIG. 31(E) and (F) show the graphs of intensity as a function of energy and the graphs of the number of electrons as a function of energy, respectively, obtained for the Sp72 region indicated in (B). It can be observed that the elongated rod-like particles are rich in Zn, while the irregularly shaped particles are devoid of Zn.

[0252] Figure 32 (A)-(F) show images obtained by TEM of MOF9. More specifically, Figure 32(A) shows an image of the irregularly shaped particles, and Figure 32(B)-(F) show images of the elongated rod-like particles boxed in (B). It can be observed that the irregularly shaped particles have amorphous carbon, while the elongated rod-like Zn-rich particles have crystalline faces.

[0253] Analysis of TEM and TEM-EDS images obtained for MOF8

[0254] FIG. 33 shows elongated rod-shaped particles having widths ranging from about 100 nm to about 200 nm, and lengths of about 1 μm.

[0255] FIG. 34 (E) shows the results of EDS analysis obtained for the areas defined in the images shown in FIGS. 34(A)-(D).

[0256] Figure 35 (G) shows the results of EDS analysis obtained for the areas defined in the images shown in Figures 35(C)-(F), which shows the substantial presence of Zn in the composition of the elongated rod-shaped particles.

[0257] Figure 36 shows irregularly shaped particles containing a substantial number of nanometric Zn particles, and (D) the results of EDS analysis obtained for the two areas indicated by the arrows in the corresponding TEM image.

[0258] Figure 37 (E) and (F) show the results of EDS analysis obtained for Region 1 (elongated rod-shaped particles) and Region 2 (irregularly shaped particles) defined in the images shown in Figures 37(A)-(D), respectively. Figure 37(E) confirms that the elongated rod-shaped particles are substantially enriched in Zn, and Figure 37(F) confirms that the irregularly shaped particles are substantially amorphous and less enriched in Zn.

[0259] FIG. 38 shows the presence of Zn nanoparticles having lengths ranging from about 2 nm to about 5 nm in a carbon matrix.

[0260] f) Effect of grinding on calcined lithiophilic MOFs

[0261] The effect of milling was also characterized by EDS using a SEM equipped with an SE detector.

[0262] 39 shows SEM images obtained for MOF8 (A) before milling, (B) after milling for about 5 minutes (SPEX™ ball mill), and (C) after milling twice for about 5 minutes. Scale bars indicate 10 μm.

[0263] Figure 40 shows (A) an SEM image of MOF8 particles after two grindings for about 5 min, with mapping images of elements C and Zn shown in (B) and (C), respectively. The scale bar indicates 5 μm.

[0264] Example 3 Preparation and characterization of calcined bimetallic lithiophilic MOFs based on Zn and Cu

[0265] a) Preparation of calcined bimetallic lithiophilic MOFs based on Zn and Cu

[0266] The calcined bimetallic lithiophilic MOF was synthesized using the method of formula 1: [ka] were prepared with various proportions of copper and zinc (Cu:Zn ratio) according to the method described above.

[0267] The MOF thus prepared was then purified by filtration and dried under vacuum at room temperature for about 18 hours.

[0268] The MOFs were calcined under an inert argon atmosphere using the following protocol. 1. Ramp from room temperature to 200°C at a rate of 1°C / min; 2. Plateau at 200℃ for 1 hour; 3. Ramp from 200°C to 750°C at a rate of 3°C / min; and 4. Plateau at 750℃ for 2 hours.

[0269] The structures of the calcined MOFs prepared in this example, the Cu:Zn ratios, and the theoretical yields after calcination determined by TGA are shown in Table 8. [Table 8]

[0270] b) Characterization of calcined bimetallic lithiophilic MOFs by TGA

[0271] The MOFs prepared in Example 3(a) were characterized by TGA to evaluate their thermal stability and their transformation process. Thermogravimetric analysis was carried out over the temperature range of about 30° C. to about 1000° C. under a constant air flow rate of 100 mL / min and a heating rate of 5° C. / min. The thermogravimetric analysis results obtained for MOFs 11-15 are shown in FIG. 41 and summarized in Table 9. [Table 9]

[0272] Figure 41 shows two mass losses that can be attributed to copper and zinc ligand halving, respectively. It can be observed that the percentage of mass loss appears to be substantially consistent with the Cu:Zn ratio.

[0273] c) SEM characterization of the calcined bimetallic lithiophilic MOF

[0274] The MOFs prepared in Example 3(a) were imaged using an SEM equipped with an SE detector. The images obtained for MOFs 11-15 are shown in Figures 42-46 and summarized in Table 10. [Table 10]

[0275] d) Characterization of calcined bimetallic lithiophilic MOFs by EDS

[0276] Elemental analysis or chemical characterization of the MOFs prepared in Example 3(a) was carried out using an SEM equipped with an X-ray detector for EDS analysis. Figures 47-51 show (A) SEM images obtained for MOFs 11 and 13-15, and (B)-(E) the corresponding EDS mapping images. The experimental conditions used for the EDS analysis performed on MOFs 11 and 13-15 are shown in Table 11. [Table 11]

[0277] 46 and 51 show that the MOF15 sample contains substantially larger Zn-rich particles and substantially smaller elongated needle-like Cu-rich particles.

[0278] e) Characterization of calcined bimetallic lithiophilic MOFs by TGA (in air)

[0279] The calcined MOFs prepared in Example 3(a) were characterized by TGA to assess their respective metal amounts. Thermogravimetric analysis was carried out under a constant air flow rate of 100 mL / min and a heating rate of 5° C. / min. The thermogravimetric analysis results obtained for MOFs 11-13 are shown in FIG. 52 and summarized in Table 12. [Table 12]

[0280] FIG. 52(B) shows that the mass loss for MOF12 calcined at a temperature of about 910° C. is slightly larger than for MOF12 calcined at a temperature of about 750° C. This can be explained by the presence of more carbon, and therefore a small amount of Zn may possibly have been lost. FIG. 52(B) also shows a substantially larger mass loss for MOF12 calcined at a temperature of about 1000° C., and the phenomenon of copper oxidation at temperatures between about 200° C. and about 400° C., indicating that little or no zinc is present.

[0281] f) Characterization of calcined and ground bimetallic lithiophilic MOFs by SEM and EDS

[0282] Figure 53 shows (A) and (B) SEM images of MOFs similar to MOF12, but calcined at a temperature of about 1000°C instead of about 750°C, and ground in a SPEX™ ball mill three times for about 5 minutes. Scale bars in (A) and (B) indicate 50.0 μm and 5.00 μm, respectively. Figure 53 shows substantially well-dispersed spherical nanometer particles in the carbon matrix.

[0283] FIG. 53(C) shows the results of the EDS analysis, which confirms the absence of Zn in the matrix, and the presence of carbon and copper.

[0284] Example 4 Preparation and characterization of calcined bimetallic lithiophilic MOFs based on Zn and Ag

[0285] a) Preparation of calcined bimetallic lithiophilic MOFs based on Zn and Ag

[0286] Calcined bimetallic lithiophilic MOFs were prepared with various ratios of zinc and silver (Zn:Ag ratio). In this way, Zn-based MOFs were synthesized according to the formula 2: [ka] It was prepared according to

[0287] The MOF thus prepared was then purified by filtration and dried in vacuum at a temperature of about 160° C. for about 20 hours.

[0288] AgNO3 was reacted with AgNO3 in the presence of the reaction product of Equation 3: [ka] was incorporated into the Zn-based MOFs by the impregnation method according to the method described above.

[0289] An aqueous solution of AgNO3 was added to the Zn-based MOF powder. The resulting solution was stirred at room temperature for about 2 hours. The water was then evaporated and the Zn- and Ag-based MOFs were dried under vacuum at room temperature for about 18 hours.

[0290] The MOFs were calcined under an inert argon atmosphere using the following protocol. 1. Ramp from room temperature to 200°C at a rate of 1°C / min; 2. Plateau at 200℃ for 1 hour; 3. Ramp from 200°C to 750°C at a rate of 3°C / min; and 4. Plateau at 750℃ for 2 hours.

[0291] The structures and Zn:Ag ratios of the calcined bimetallic MOFs prepared in this example are shown in Table 13. [Table 13]

[0292] b) Characterization of calcined bimetallic lithiophilic MOFs by TGA

[0293] The MOFs prepared in Example 4(a) were characterized by TGA to evaluate their thermal stability and their transformation process. Thermogravimetric analysis was carried out over a temperature range of about 30° C. to about 1000° C. under a constant air flow rate of 100 mL / min and a heating rate of 5° C. / min. The thermogravimetric analysis results obtained for MOFs 16-19 are shown in FIG. 54 and summarized in Table 14. [Table 14]

[0294] FIG. 54 shows the mass loss at temperatures below 300° C., which can be attributed to silver.

[0295] c) Surface characterization of calcined bimetallic lithiophilic MOFs by BET method

[0296] The pore size, specific surface area, and pore volume of the calcined MOF prepared in Example 4(a) were characterized.

[0297] Nitrogen adsorption / desorption isotherms (graphs of the volume of adsorbed nitrogen as a function of the relative nitrogen pressure P / P0) were obtained for each of the MOFs prepared in Example 4(a). The pore size, pore volume distribution, specific surface area, and total pore volume were extracted from these isotherms. The pore size was determined using the BdB method. The pore volume distribution was determined by the BJH method. The specific surface area and pore volume were calculated using the BET method.

[0298] FIG. 55 shows (A) nitrogen adsorption / desorption isotherms, (B) graphs of the distribution of pore volume as a function of pore width, (C) graphs of specific surface area as a function of pore width, and (D) graphs of total pore volume as a function of pore width, obtained for MOFs 16 (squares), 17 (triangles), 18 (circles), and 19 (stars). It can be observed that the more silver salt is incorporated, the more the BET surface area is reduced and pores with widths from about 3.5 nm to about 6 nm are filled. A substantial proportion of the specific surface area arises from mesopores with widths from about 2 nm to about 8 nm. Thus, the method of incorporating silver salts into the mesopores appears to be effective.

[0299] d) SEM characterization of calcined bimetallic lithiophilic MOFs

[0300] The MOFs prepared in Example 4(a) were imaged using an SEM equipped with an SE detector. The images obtained for MOFs 16-19 are shown in Figures 56-59 and summarized in Table 15. [Table 15]

[0301] Figures 56-59 show heterogeneous mixtures containing particles of various sizes and shapes.

[0302] e) Characterization of calcined bimetallic lithiophilic MOFs by EDS

[0303] Elemental analysis or chemical characterization of the MOF prepared in Example 4(a) was carried out using a SEM equipped with an X-ray detector for EDS analysis.

[0304] 60 shows (A) an SEM image obtained for MOF16, and (B) a graph showing the results of an EDS analysis obtained for the area defined in (A). The scale bar indicates 10 μm.

[0305] 61 and 62 show (A) SEM images obtained for MOFs 16-18, and (B)-(E) the corresponding EDS mapping images. The experimental conditions used for the EDS analyses performed on MOFs 17 and 18 are shown in Table 16. [Table 16]

[0306] Example 5 Preparation and characterization of Mg-based lithiophilic MOFs and bimetallic Mg- and Zn-based lithiophilic MOFs

[0307] a) Preparation of Mg-based lithiophilic MOFs and bimetallic Mg- and Zn-based lithiophilic MOFs

[0308] A Mg-based lithiophilic MOF was prepared from magnesium carbonate hydroxide pentahydrate ((MgCO3)4Mg(OH)25H2O) and H4btec. Two bimetallic MOFs based on Mg and Zn were prepared from (MgCO3)4Mg(OH)25H2O, ZnO, and H4btec. The thus-prepared MOFs were then purified by filtration and dried in vacuum at room temperature for about 18 hours.

[0309] The MOFs prepared in this example are shown in Table 17. [Table 17]

[0310] b) Characterization of Mg-based lithiophilic MOFs by TGA

[0311] The MOFs prepared in Example 5(a) were characterized by TGA to evaluate their thermal stability and their transformation process. Thermogravimetric analysis was carried out over a temperature range of about 30° C. to about 1000° C. under a constant air flow rate of 100 ml / min and a heating rate of 5° C. / min. The thermogravimetric analysis results obtained for MOFs 20 and 21 are shown in FIG. 63 and summarized in Table 18. [Table 18]

[0312] c) SEM characterization of Mg-based lithiophilic MOFs

[0313] The MOFs prepared in Example 5(a) were imaged using an SEM equipped with an SE detector. The images obtained for MOFs 20-22 are shown in Figures 64-66 and summarized in Table 19. [Table 19]

[0314] Figure 65(D) and (E) show SEM images of MOF21 obtained after calcination at a temperature of about 750° C. The appearance of substantial small spheres on the carbon surface after calcination can be observed.

[0315] Figure 66(D) and (E) show SEM images of MOF22 obtained after calcination at a temperature of about 1000° C. The appearance of substantial small spheres in the carbon matrix after calcination can be observed.

[0316] d) Characterization of Mg-based lithiophilic MOFs by EDS

[0317] Elemental analysis or chemical characterization of MOF21 and 22 prepared in Example 5(a) was carried out using SEM equipped with an X-ray detector for EDS analysis. Figure 67 shows (A) an SEM image obtained for MOF21 before calcination, and (B)-(E) corresponding EDS mapping images. Figure 68 shows (A) an SEM image obtained for MOF21 after calcination at a temperature of about 750°C, (B)-(E) corresponding EDS mapping images, and (F) corresponding EDS analysis results. Figure 69 shows (A) an SEM image obtained for MOF22 before calcination, and (B)-(F) corresponding EDS mapping images. Figure 70 shows (A) an SEM image obtained for MOF22 after calcination at a temperature of about 1000°C, (B)-(E) corresponding EDS mapping images, and (F) corresponding EDS analysis results. The experimental conditions used for the EDS analysis carried out on MOF21 and 22 are shown in Table 20. [Table 20]

[0318] The results of the EDS analysis obtained for MOF21 after calcination at a temperature of about 750° C. are shown in Table 21. A significant amount of oxygen (about 17.85 atomic %) can be observed, which is substantially close to the sum of zinc and magnesium (about 16 atomic %). This indicates that metal oxides such as magnesium oxide (MgO) and ZnO are possibly formed. It can also be observed in the EDS spectrum that the zinc-rich regions are also rich in oxygen. [Table 21]

[0319] The results of the EDS analysis obtained for MOF22 before calcination at a temperature of about 1000° C. are given in Table 22. The results shown in Table 22 were obtained in the boxed area of ​​the SEM image in Figure 69(A). It can be observed that the composition varies depending on the shape of the particles. [Table 22]

[0320] The results of the EDS analysis obtained for MOF22 after calcination at a temperature of about 1000° C. are shown in Table 23. It can be observed that the spheres present in the carbon matrix are enriched in oxygen and metals such as zinc and magnesium, again suggesting that metal oxides such as MgO and ZnO may be formed. [Table 23]

[0321] Example 6 Preparation and characterization of Mg-based lithiophilic MOFs

[0322] a) Preparation of Mg-based lithiophilic MOFs

[0323] The Mg-based lithiophilic MOF was synthesized using the formula 4: [ka] It was prepared from magnesium carbonate (MgCO3) or magnesium acetate (Mg(OAc)2) and H4btec according to

[0324] The MOFs thus prepared were then purified by filtration and dried under vacuum at room temperature for about 18 hours. The MOFs prepared in this example are shown in Table 24. [Table 24]

[0325] It was observed that Mg(OAc)2 appears to be a suitable precursor for the synthesis of Mg-based MOFs.

[0326] b) SEM characterization of Mg-based lithiophilic MOFs

[0327] The MOFs prepared in Example 6(a) were imaged using an SEM equipped with an SE detector. The images obtained for MOFs 23 and 24 are shown in Figures 71 and 72 and summarized in Table 25. [Table 25]

[0328] c) Characterization of Mg-based lithiophilic MOFs by EDS

[0329] Elemental analysis or chemical characterization of the MOFs prepared in Example 6(a) was carried out using an SEM equipped with an X-ray detector for EDS analysis. Figures 73 and 74 show (A) SEM images obtained for MOFs 23 and 24, respectively, (B)-(D) EDS mapping images, and (E) the results of the corresponding EDS analysis. The experimental conditions used for the EDS analysis performed on MOFs 23 and 24 are shown in Table 26. [Table 26]

[0330] Example 7 Preparation and characterization of bimetallic lithiophilic MOFs based on Sb and Zn

[0331] a) Preparation of bimetallic lithiophilic MOFs based on Sb and Zn

[0332] The bimetallic lithiophilic MOF based on Sb and Zn was synthesized using the formula 5: [ka] It was prepared from antimony(III) acetate (Sb(OAc)3), ZnO, and H4btec according to the method described in

[20] .

[0333] The MOF thus prepared was then purified by filtration and dried under vacuum at room temperature for about 18 hours.

[0334] The structures and Sb:Zn ratios of the bimetallic MOFs prepared in this example are shown in Table 27. [Table 27]

[0335] b) SEM characterization of bimetallic lithiophilic MOFs

[0336] The MOFs prepared in Example 7(a) were imaged using an SEM equipped with an SE detector. The images obtained for MOFs 25-30 are shown in Figures 75-80 and summarized in Table 28. [Table 28]

[0337] c) Characterization of bimetallic lithiophilic MOFs by EDS

[0338] Elemental analysis or chemical characterization of the MOFs prepared in Example 7(a) was carried out using an SEM equipped with an X-ray detector for EDS analysis. Figures 81-86 show (A) SEM images obtained for MOFs 25-30, respectively, and (B)-(D) or (E) EDS mapping images. The experimental conditions used for the EDS analysis carried out on MOFs 25-30 are shown in Table 29. [Table 29]

[0339] Example 8 Preparation and characterization of Zn- and Ag-based bimetallic lithiophilic MOFs with bifunctional ligands

[0340] a) Preparation of bimetallic lithiophilic MOFs based on Zn and Ag with bifunctional ligands

[0341] A bimetallic lithiophilic MOF based on Zn and Ag with bifunctional ligands was synthesized according to the formula 7: [ka] It was prepared from commercially available bifunctional ligands according to

[0342] Bimetallic lithiophilic MOFs based on Zn and Ag with bifunctional ligands were also prepared according to formulas 8 and 9: [ka] It was prepared from a synthetic bifunctional ligand according to

[0343] The structures and Zn:Ag ratios of the bimetallic MOFs prepared in this example are shown in Table 30. [Table 30]

[0344] b) SEM characterization of bimetallic lithiophilic MOFs

[0345] The MOFs prepared in Example 8(a) were imaged using an SEM equipped with an SE detector. The images obtained for MOFs 31 and 32 are shown in Figures 87-89 and summarized in Table 31. [Table 31]

[0346] c) Characterization of bimetallic lithiophilic MOFs by EDS

[0347] Elemental analysis or chemical characterization of the MOFs prepared in Example 8(a) was carried out using an SEM equipped with an X-ray detector for EDS analysis. Figures 90-92 show (A) SEM images and (B)-(E) EDS mapping images obtained for MOFs 31 and 32, respectively. The experimental conditions used for the EDS analysis performed on MOFs 31 and 32 are shown in Table 32. [Table 32]

[0348] The results of the EDS analysis obtained for MOF32 after calcination at a temperature of about 1000° C. are shown in FIG. 93. The results shown in FIG. 93 were obtained in the boxed area of ​​the image shown in FIG. 93. FIG. 93 shows (A) the combined results of the EDS analysis, (B) the results of the EDS analysis obtained for spectrum 14, and (C) the results of the EDS analysis obtained for spectrum 15. The results of the EDS analysis obtained are summarized in Table 33. [Table 33]

[0349] The results show that a carbon-rich powder is obtained with a substantially uniform distribution of silver in the calcined MOF (about 73 at.% to about 83 at.%, depending on the observation area). The presence of trace amounts of zinc can be observed. However, oxygen is substantially absent or present only in very small amounts. It can be concluded that the metal is formed mainly in elemental form.

[0350] Example 9 Electrochemical cell preparation and characterization

[0351] a) Preparation of coating materials based on calcined lithiophilic MOFs

[0352] A coating material based on calcined lithiophilic MOF as described in the previous examples was prepared. The coating material was obtained by mixing MOF with a 60 wt% solution of solid polymer electrolyte containing LiTFSI in a solvated polymer with a polymer:LiTFSI ratio of (20:1) as described in U.S. Patent No. 6,903,174 B2 (Harvey et al.) (US'174) and 40 wt% tetraethylene glycol dimethyl ether. The composition of the coating material is shown in Table 34. [Table 34]

[0353] b) Electrochemical cell configuration

[0354] The electrochemical properties of the coating material prepared in Example 9(a) were studied.

[0355] The electrochemical cell was assembled with one or two coating layers, a first coating layer being crosslinked and a second layer being non-crosslinked and disposed between the first coating layer and the electrolyte, the second coating layer allowing for a substantial improvement in adhesion between the various components of the electrochemical cell and thus improved electrochemical performance.

[0356] The electrochemical cell was assembled with a lithium iron phosphate positive electrode (LiFePO4, LFP) on a carbon-coated aluminum current collector (Armor™). The composition of the electrochemically active material of the positive electrode is shown in Table 35. [Table 35]

[0357] All electrochemical cells were assembled with a self-supporting solid polymer electrolyte as described in the US '174 patent, containing 81.8 wt% polymer, 17.8 wt% LiTFSI and 0.4 wt% 2,2-dimethoxy-2-phenylacetophenone (Irgacure™ 651).

[0358] The electrochemical cell was assembled with a lubricated lithium metal negative electrode having a thickness of about 50 μm on a copper current collector.

[0359] The electrochemical cell was assembled according to the configuration shown in Table 36. [Table 36]

[0360] Cells 2-9 were assembled with a second coating layer containing 60% by weight of polymer and LiTFSI as described in US '174 with a polymer:LiTFSI ratio of (20:1), and 40% by weight of tetraethylene glycol dimethyl ether. The polymer in the second layer was not crosslinked.

[0361] A reference electrochemical cell was assembled according to the configuration shown in Table 37. [Table 37]

[0362] c) Electrochemical behavior

[0363] Electrochemical analysis demonstrated that the second coating layer significantly improved the adhesion between the first coating layer and the electrolyte. The presence of this second coating layer also appears to improve the reproducibility of the electrochemical results while improving the coulombic efficiency and initial discharge capacity. Improved electrochemical performance was also observed for electrochemical cells containing thinner first coating layer films.

[0364] Figure 94 shows a graph of capacity as a function of cycle number obtained at charge / discharge currents of C / 6, C / 4, C / 3, C / 2 and 1C for cells 8 (triangles) and 9 (inverted triangles) and references 3 (squares) and 4 (circles). Better reproducibility of electrochemical performance was observed for electrochemical cells containing thicker second coating layer films. Figure 94 shows that electrochemical performance is substantially close to that of the two references, despite the total coating layer thickness of about 26 μm.

[0365] Example 10 Deposition of layers of calcined lithiophilic MOFs by sputtering

[0366] a) Deposition of a layer of calcined lithiophilic MOF by sputtering

[0367] A layer of the calcined lithiophilic MOF was deposited onto lithium foil by sputtering.

[0368] The calcined lithiophilic MOF was dispersed in tetrahydrofuran (THF) at a concentration of about 1.5 mg / mL. 100 mL of the resulting solution was mixed in an ultrasonic bath for about 15 minutes. The solution was then placed in a manual spray coater in an anhydrous chamber. A lithium foil measuring about 8 cm x 15 cm was placed flat, face up, on a hard substrate and firmly fixed. Spraying was performed by applying a dry air pressure of about 60 psi at a distance of about 30 cm. Two spray passes were made from above to below the lithium foil surface. The lithium foil was dried overnight under vacuum at a temperature of about 50°C.

[0369] Depositions were carried out with MOFs 11 and 12, calcined bimetallic lithiophilic MOFs based on Zn and Cu.

[0370] b) SEM characterization of calcined lithiophilic MOF layers obtained by sputtering

[0371] The calcined lithiophilic MOF layers deposited in Example 10(a) were imaged using an SEM equipped with an SE detector. The images obtained for two layers of MOFs 11 and 12 are shown in Figures 95 and 96 and summarized in Table 38. [Table 38]

[0372] Figure 95 shows an image obtained by SEM of a cross section of a lithium foil coated with a layer of calcined lithiophilic MOF (MOF11 calcined at 750°C) obtained by sputtering. A layer of calcined lithiophilic MOF with a thickness ranging from a few hundred nm to about 1 µm can be observed.

[0373] Figure 96 shows an image obtained by SEM of a cross section of a lithium foil coated with a layer of calcined lithiophilic MOF (MOF12 calcined at 1000°C) obtained by sputtering. A layer of calcined lithiophilic MOF with a thickness ranging from about 900 nm to about 1 µm can be observed.

[0374] c) EDS characterization of calcined lithiophilic MOF layers obtained by sputtering

[0375] Elemental analysis or chemical characterization of the calcined lithiophilic MOF layer deposited in Example 10(a) was carried out using a SEM equipped with an X-ray detector for EDS analysis.

[0376] FIG. 97 shows the EDS mapping image obtained for layer 1.

[0377] FIG. 98 shows (A) an SEM image obtained for layer 2, and (B)-(D) EDS mapping images.

[0378] FIG. 99 shows the EDS mapping image obtained for layer 2.

[0379] The experimental conditions used for the EDS analysis carried out on the calcined lithiophilic MOF layers obtained by sputtering are given in Table 39. [Table 39]

[0380] Figure 97 shows (A) an SEM image obtained for a layer of calcined lithiophilic MOF (MOF11 calcined at 750°C) obtained by sputtering, as well as EDS mapping of Zn (blue), Cu (green) and Al (red). Figure 97(B) and (C) show the Cu and Zn EDS mapping images, respectively, obtained for the area defined in (A). The presence of both metals (Cu and Zn), mainly Cu, can be observed.

[0381] FIG. 98 shows (A) an SEM image obtained for a layer of calcined lithiophilic MOF (MOF12 calcined at 1000° C.) obtained by sputtering, (B) SEM images and EDS mapping of Cu (pink), Al (blue), O (green) and C (red), and (C) and (D) EDS mapping images of Cu and C obtained for the areas defined in (A) and (B), respectively. The absence of Zn can be observed due to its evaporation at high temperature. Nanometric spheres of Cu can be observed on the lithium side of the layer of calcined lithiophilic MOF obtained by sputtering. The presence of these spheres can be attributed to the low-temperature cut, which can result in hard metal particles.

[0382] FIG. 99 shows (A) an SEM image obtained for a layer of calcined lithiophilic MOF (MOF12 calcined at 1000° C.) obtained by sputtering, as well as EDS mapping of O (green) and C (red). FIG. 99(B) and (C) show EDS mapping images of C and O, respectively, obtained for the area defined in (A). The absence of Cu and Zn can be observed; the latter are evaporated to create porosity and prevent the formation of copper particles.

[0383] d) Electrochemical behavior of calcined lithiophilic MOF layers obtained by sputtering

[0384] The electrochemical properties of the calcined lithiophilic MOF layer obtained by sputtering, prepared in Example 10(a), were investigated.

[0385] An electrochemical cell was assembled with a lithium metal negative electrode comprising a layer of the calcined lithiophilic MOF prepared in Example 10(a) deposited by sputtering on the surface of lithium foil on a copper current collector. The electrochemical cell was assembled without a coating layer.

[0386] The electrochemical cell was assembled with the LFP positive electrode on a carbon coated aluminum current collector (Armor™). The composition of the electrochemically active material of the positive electrode is shown in Table 35 of Example 9(b).

[0387] All electrochemical cells were assembled with a self-supporting solid polymer electrolyte as described in the US '174 patent, containing 81.8 wt% polymer, 17.8 wt% LiTFSI and 0.4 wt% 2,2-dimethoxy-2-phenylacetophenone (Irgacure™ 651).

[0388] The electrochemical cell was assembled according to the configuration shown in Table 40. [Table 40]

[0389] A reference electrochemical cell was assembled according to the configuration shown in Table 41. [Table 41]

[0390] FIG. 100 shows a graph of capacity as a function of cycle number obtained at charge / discharge currents of C / 6, C / 4, C / 3, C / 2 and 1C for cells 10 (square), 11 (circle), 12 (triangle) and 13 (inverted triangle) and references 5 (star) and 6 (hexagon).

[0391] FIG. 101 shows a graph of the coulombic efficiency as a function of cycle number obtained for cells 10 (squares), 11 (circles), 12 (triangles) and 13 (inverted triangles), as well as references 5 (stars) and 6 (hexagons).

[0392] It can be observed that the electrochemical performance is very close to the reference cells, especially for cells 10 and 11.

[0393] Several modifications can be made to any of the above embodiments without departing from the scope of the invention as contemplated. All references, patent or scientific literature mentioned in this application are incorporated herein by reference in their entirety for all purposes.

Claims

1. 1. A method for preparing a negative electrode material comprising an electrochemically active material and a coating layer comprising a calcined lithiophilic organometallic structure-based coating material disposed on a surface of the electrochemically active material, the method comprising the steps of: (i) contacting at least one organic ligand with at least one lithiophilic metal precursor to obtain a lithiophilic organometallic structure; (ii) calcining the lithiophilic organometallic structure obtained in (i) to obtain the calcined lithiophilic organometallic structure of the coating material; (iii) depositing the coating material on a surface of the electrochemically active material; A method comprising:

2. 2. The method of claim 1, wherein the lithiophilic metal is selected from Ag, Zn, Sn, Sb, Mg, Al, Ni, Cu, Co, and combinations of at least two thereof.

3. 3. The method of claim 1 or 2, wherein the organic ligand is an organic ligand containing a nitrogen functional group, an organic ligand containing a carboxylate, or a mixed organic ligand containing a nitrogen functional group and / or a carboxylate.

4. The method of claim 3, wherein the organic ligand is 1,2,4,5-benzenetetracarboxylic acid or 1H-benzimidazole-6-carboxylic acid.

5. The lithiophilic organometallic structure obtained in (i) is represented by the formula 1: 【Chemical 33】 The method according to any one of claims 1 to 4,

6. The lithiophilic organometallic structure obtained in (i) is represented by formula 2: 【Chemical 34】 The method according to any one of claims 1 to 4,

7. The lithiophilic organometallic structure obtained in (i) is represented by formula 3: 【Chemistry 35】 The method according to any one of claims 1 to 4,

8. The lithiophilic organometallic structure obtained in (i) is represented by formula 4: 【Chemical 36】 The method according to any one of claims 1 to 4,

9. The lithiophilic organometallic structure obtained in (i) is represented by formula 5: 【Chemical 37】 The method according to any one of claims 1 to 4,

10. The lithiophilic organometallic structure obtained in (i) is represented by formula 6: 【Chemical 38】 (In the formula, n 1 and n 2 indicates the ratio of each unit and is an independently selected number ranging from 0.1 to 0.9) The method according to any one of claims 1 to 4,

11. The lithiophilic organometallic structure obtained in (i) is represented by formula 7: 【Chemical 39】 (In the formula, n 1 and n 2 indicates the ratio of each unit and is an independently selected number ranging from 0.1 to 0.9) The method according to any one of claims 1 to 4,

12. The lithiophilic organometallic structure obtained in (i) is represented by formula 8: 【Chemistry 40】 (In the formula, n 1 and n 2 indicates the ratio of each unit and is an independently selected number ranging from 0.1 to 0.9) The method according to any one of claims 1 to 4,

13. The lithiophilic organometallic structure obtained in (i) is represented by formula 9: 【Chemistry 41】 The method according to any one of claims 1 to 4,

14. The method of any one of claims 1 to 13, wherein the calcination step is carried out at a temperature of from about 500°C to about 1050°C.

15. The method of claim 14, wherein the calcination step is carried out at a temperature of from about 550° C. to about 1000° C.

16. The method according to any one of claims 1 to 15, wherein the calcination step is carried out under an inert atmosphere.

17. 17. The method of claim 16, wherein the inert atmosphere comprises a gas selected from argon, oxygen, nitrogen, helium, a fluorinated gas, and a mixture comprising at least two of the same.

18. The method of claim 17 , wherein the inert atmosphere comprises argon.

19. 19. The method according to any one of the preceding claims, wherein the depositing step is carried out by at least one of the following printing methods: doctor blade coating, comma coating, reverse comma coating, gravure coating, slot die coating, or spray deposition.

20. The method of claim 19 , wherein the depositing step is performed by a spray deposition process.

21. The method of any one of claims 1 to 20, further comprising the step of depositing a second coating layer.

22. 22. The method of claim 21, wherein the step of depositing the second coating layer is performed by at least one of a doctor blade coating method, a comma coating method, a reverse comma coating method, a printing method such as gravure coating, a slot die coating method, or a spray deposition method.

23. 23. The method of claim 22, wherein the step of depositing the second coating layer is performed by spray deposition.

24. A negative electrode material obtained according to a method as defined in any one of claims 1 to 23.

25. 1. A negative electrode material comprising an electrochemically active material and a coating layer comprising a coating material based on a calcined lithiophilic organometallic structure comprising at least one lithiophilic metal and at least one at least partially calcined organic ligand, said coating layer being disposed on a surface of said electrochemically active material.

26. 26. The electrode material of claim 25, wherein the electrochemically active material comprises an alkali metal, an alkaline earth metal, a non-alkali and non-alkaline earth metal, or an alloy comprising at least one thereof.

27. 27. The electrode material of claim 26, wherein the electrochemically active material comprises an alkali metal, an alkaline earth metal, or an alloy containing at least one alkali or alkaline earth metal.

28. 28. The electrode material of claim 27, wherein the electrochemically active material comprises metallic lithium or an alloy comprising or based on metallic lithium.

29. 27. The electrode material of claim 26, wherein the electrochemically active material comprises nickel.

30. 30. The electrode material of any one of claims 25 to 29, wherein the electrochemically active material is in the form of a film having a thickness in the range of about 5 μm to about 75 μm, or about 15 μm to about 70 μm, or about 25 μm to about 65 μm, or about 30 μm to about 60 μm, or about 45 μm to about 55 μm, inclusive.

31. 31. The electrode material according to any one of claims 25 to 30, wherein the lithiophilic metal is selected from Ag, Zn, Sn, Sb, Mg, Al, Ni, Cu, Co, and combinations of at least two thereof.

32. 32. The electrode material according to any one of claims 25 to 31, wherein the organic ligand is an organic ligand comprising a nitrogen functional group, an organic ligand comprising a carboxylate, or a mixed organic ligand comprising a nitrogen functional group and / or a carboxylate.

33. The electrode material according to claim 32, wherein the organic ligand is 1,2,4,5-benzenetetracarboxylic acid or 1H-benzimidazole-6-carboxylic acid.

34. The lithiophilic organometallic structure prior to calcination has the formula 1: 【Chemistry 42】 The electrode material according to any one of claims 25 to 33,

35. The lithiophilic organometallic structure prior to calcination has the formula 2: 【Chemistry 43】 The electrode material according to any one of claims 25 to 33,

36. The lithiophilic organometallic structure prior to calcination has the formula 3: 【Chemistry 44】 The electrode material according to any one of claims 25 to 33,

37. The lithiophilic organometallic structure prior to calcination has the formula 4: 【Chemistry 45】 The electrode material according to any one of claims 25 to 33,

38. The lithiophilic organometallic structure prior to calcination has the formula 5: 【Chemistry 46】 The electrode material according to any one of claims 25 to 33,

39. The lithiophilic organometallic structure prior to calcination has the formula 6: 【Chemistry 47】 (In the formula, n 1 and n 2 indicates the ratio of each unit and is an independently selected number ranging from 0.1 to 0.9) The electrode material according to any one of claims 25 to 33,

40. The lithiophilic organometallic structure prior to calcination has the formula 7: 【Chemistry 48】 (In the formula, n 1 and n 2 indicates the ratio of each unit and is an independently selected number ranging from 0.1 to 0.9) The electrode material according to any one of claims 25 to 33,

41. The lithiophilic organometallic structure prior to calcination has the formula 8: 【Chemistry 49】 (In the formula, n 1 and n 2 indicates the ratio of each unit and is an independently selected number ranging from 0.1 to 0.9) The electrode material according to any one of claims 25 to 33,

42. The lithiophilic organometallic structure prior to calcination has the formula 9: 【Chemistry 50】 The electrode material according to any one of claims 25 to 33,

43. 43. The electrode material of any one of claims 25 to 42, wherein the calcined lithiophilic organometallic structure further comprises a silver source.

44. 44. The electrode material of claim 43, wherein the silver source is a silver salt.

45. The silver salt is AgCl or AgNO 3 45. The electrode material of claim 44,

46. 46. ​​The electrode material of claim 44 or 45, wherein the salt is present in a lithiophilic metal:silver ratio in the range of about 4:3 to about 4:1, inclusive.

47. Electrode material according to any one of claims 25 to 46, wherein the coating material further comprises a solid polymer electrolyte comprising a salt in a solvated polymer.

48. 48. The electrode material of claim 47, wherein the solid polymer electrolyte is a copolymer of ethylene oxide and at least one substituted oxirane that contains a crosslinkable functional group.

49. The copolymer comprises ethylene oxide based units and -O-CH 2 49. The electrode material of claim 48, comprising -CHR units, where R is a substituent containing a radical crosslinkable functional group and is independently selected from each other unit.

50. The copolymer is -O-CH 2 50. The electrode material of claim 49, further comprising -CHR' units, where R' is a substituent that does not contain a radical crosslinkable functional group and is independently selected from each other unit.

51. The copolymer has a multimolecularity index (I=M w / M n ) (in the formula, M n is the number average molecular weight of the copolymer, greater than or equal to 20,000; M w The electrode material according to any one of claims 48 to 50, wherein Mn is a weight average molecular weight.

52. 52. The electrode material according to any one of claims 48 to 51, wherein the copolymer is crosslinked.

53. The electrode material according to any one of claims 47 to 52, wherein the salt is a lithium salt.

54. The lithium salt is lithium hexafluorophosphate (LiPF 6 ), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium 2-trifluoromethyl-4,5-dicyanoimidazolate (LiTDI), lithium 4,5-dicyano-1,2,3-triazolate (LiDCTA), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium tetrafluoroborate (LiBF 4 ), lithium bis(oxalato)borate (LiBOB), lithium nitrate (LiNO 3 ), lithium chloride (LiCl), lithium bromide (LiBr), lithium fluoride (LiF), lithium perchlorate (LiClO 4 ), lithium hexafluoroarsenate (LiAsF 6 ), lithium trifluoromethanesulfonate (LiSO 3 CF 3 ) (LiOTf), lithium fluoroalkyl phosphate Li[PF 3 (CF 2 CF 3 ) 3 ] (LiFAP), lithium tetrakis(trifluoroacetoxy)borate Li[B(OCOCF 3 ) 4 ] (LiTFAB), lithium bis(1,2-benzenediolato(2-)-O,O')borate Li[B(C 6 O 2 ) 2 ] (LiBBB), and combinations of at least two thereof.

55. 55. The electrode material of claim 54, wherein the lithium salt is LiTFSI.

56. 56. The electrode material of any one of claims 25 to 55, wherein the coating layer has a thickness in the range of about 1 μm to about 20 μm, or about 1 μm to about 19 μm, or about 1 μm to about 18 μm, or about 1 μm to about 17 μm, or about 1 μm to about 16 μm, or about 1 μm to about 15 μm, or about 1 μm to about 14 μm, or about 1 μm to about 13 μm, or about 2 μm to about 12 μm, inclusive.

57. 57. The electrode material of claim 56, wherein the coating layer has a thickness in the range of about 2 μm to about 12 μm, inclusive.

58. 58. The electrode material of any one of claims 25 to 57, wherein the electrochemically active material is lubricated.

59. 59. The electrode material of any one of claims 25 to 58, wherein the coating layer is a first coating layer and the electrode material comprises a second coating material layer.

60. 60. The electrode material of claim 59, wherein the second coating layer has a thickness in the range of about 1 μm to about 20 μm, or about 1 μm to about 19 μm, or about 1 μm to about 18 μm, or about 1 μm to about 17 μm, or about 1 μm to about 16 μm, or about 1 μm to about 15 μm, or about 1 μm to about 14 μm, or about 2 μm to about 14 μm, inclusive.

61. 61. The electrode material of claim 60, wherein the thickness of the second coating layer is in the range of about 2 μm to about 14 μm, inclusive.

62. 62. The electrode material of any one of claims 59 to 61, wherein the second coating layer comprises a non-crosslinked polymer.

63. 63. A method for preparing an electrode material as defined in any one of claims 25 to 62, comprising the step of depositing said coating layer based on a calcined lithiophilic organometallic structure on the surface of said electrochemically active material.

64. 64. The method of claim 63, further comprising depositing the second coating layer.

65. 65. The method of claim 63 or 64, wherein the depositing step is carried out by at least one of a printing method such as doctor blade coating, comma coating, reverse comma coating, gravure coating, a slot die coating, or a spray deposition method.

66. 66. The method of claim 65, wherein the depositing step is performed by spray deposition.

67. 67. The method of any one of claims 63 to 66, further comprising preparing said coating layer based on said calcined lithiophilic organometallic structure.

68. 68. The method of claim 67, wherein said preparation of said coating layer based on a calcined lithiophilic organometallic structure further comprises the step of preparing said calcined lithiophilic organometallic structure.

69. 69. The method of claim 68, wherein the step of preparing the calcined lithiophilic organometallic structure comprises the steps of: (i) contacting at least one organic ligand with at least one lithiophilic metal precursor to obtain a lithiophilic organometallic structure; and (ii) calcining the lithiophilic organometallic structure obtained in (i) to obtain the calcined lithiophilic organometallic structure.

70. 65. A negative electrode comprising on a current collector an electrode material as defined in any one of claims 24 to 62 or an electrode material obtained according to a method as defined in any one of claims 1 to 23 or 63 to 69.

71. A self-supporting negative electrode comprising an electrode material as defined in any one of claims 24 to 62 or obtained according to a method as defined in any one of claims 1 to 23 or 63 to 69.

72. 11. An electrochemical cell comprising a negative electrode, a positive electrode and an electrolyte, wherein the negative electrode is as defined in claim 70 or 71 or comprises an electrode material as defined in any one of claims 24 to 62.

73. 73. The electrochemical cell of claim 72, wherein the positive electrode comprises an electrochemically active material selected from a metal oxide, a metal sulfide, a metal oxysulfide, a metal phosphate, a metal fluorophosphate, a metal oxyfluorophosphate, a metal sulfate, a metal halide, a metal fluoride, sulfur, selenium, and combinations of at least two thereof.

74. 74. The electrochemical cell of claim 73, wherein the metal of the electrochemically active material is selected from titanium (Ti), iron (Fe), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), chromium (Cr), copper (Cu), zirconium (Zr), niobium (Nb), and combinations of at least two thereof.

75. 75. The electrochemical cell of claim 73 or 74, wherein the metal of the electrochemically active material further comprises an alkali or alkaline earth metal selected from lithium (Li), sodium (Na), potassium (K), and magnesium (Mg).

76. 76. The electrochemical cell of any one of claims 73 to 75, wherein the electrochemically active material is lithium metal phosphate.

77. The lithium metal phosphate is LiFePO 4 77. The electrochemical cell of claim 76, wherein:

78. 78. An electrochemical cell according to any one of claims 72 to 77, wherein the electrolyte is a solid polymer electrolyte comprising a salt in a solvating polymer.

79. 78. An electrochemical cell according to any one of claims 72 to 77, wherein the electrolyte is a liquid electrolyte comprising a salt in a solvent.

80. Electrochemical cell according to any one of claims 72 to 77, wherein the electrolyte is a gel electrolyte comprising a salt in a solvent and optionally a solvating polymer.

81. 81. An electrochemical cell according to any one of claims 78 to 80, wherein the salt is a lithium salt.

82. The lithium salt is lithium hexafluorophosphate (LiPF 6 ), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium 2-trifluoromethyl-4,5-dicyanoimidazolate (LiTDI), lithium 4,5-dicyano-1,2,3-triazolate (LiDCTA), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium tetrafluoroborate (LiBF 4 ), lithium bis(oxalato)borate (LiBOB), lithium nitrate (LiNO 3 ), lithium chloride (LiCl), lithium bromide (LiBr), lithium fluoride (LiF), lithium perchlorate (LiClO 4 ), lithium hexafluoroarsenate (LiAsF 6 ), lithium trifluoromethanesulfonate (LiSO 3 CF 3 ) (LiOTf), lithium fluoroalkyl phosphate Li[PF 3 (CF 2 CF 3 ) 3 ] (LiFAP), lithium tetrakis(trifluoroacetoxy)borate Li[B(OCOCF 3 ) 4 ] (LiTFAB), lithium bis(1,2-benzenediolato(2-)-O,O')borate Li[B(C 6 O 2 ) 2 ] (LiBBB), and combinations of at least two thereof.

83. 83. The electrochemical cell of claim 82, wherein the lithium salt is LiTFSI.

84. A battery comprising at least one electrochemical cell as defined in any one of claims 72 to 83.

85. 85. The battery of claim 84, wherein the battery is selected from the group consisting of a lithium battery, a lithium ion battery, a sodium battery, a sodium ion battery, a potassium battery, a potassium ion battery, a magnesium battery, and a magnesium ion battery.

86. 86. The battery of claim 84 or 85, wherein the battery is a lithium battery.

87. 86. The battery of claim 84 or 85, wherein the battery is a lithium ion battery.